Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Enhancing in-situ primary sludge fermentation by limited sludge recirculation and solids retention time regulation in a full-scale wastewater treatment plant - Jiaxiang Nie; Ji Zhao; Yang Li; Jimiao Wang; Yong Qu; Yan Zhang; Yanling Qiu; Juan Feng; Xiaoxia Wang (Bioresource Technology, 2026)

Hypoxia-preconditioned bone marrow mesenchymal stem cells alleviate acute liver failure in association with the VEGF/c-Met pathway - Mei-Mei Lan; Rui-Zhi Shi; Zhe-Yu Li; Wen-Jun Qiao; Yong-Juan Guan; Wen-Qiang He; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

FSH inhibits mitophagy via the mTOR/TFEB axis to preserve mitochondrial function in goat Sertoli cells - Huaming Xi; Feng Jiang; Xianglong Wang; Juan Li; Dong Niu (Theriogenology, 2026)

SnRK2 and MLKs orchestrate FREE1 nuclear retention through phosphorylation to regulate ABA signaling in Arabidopsis - Zien Li; Fanfan Qiao; Fei Rao; Juan Wei; Chuanliang Liu; Lei Feng; Jun Ma; Lu Dai; Lidan Zhang; Caiji Gao; Yanglan Liao; Wenjin Shen; et al. (Plant Science, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Microbial community dynamics and functional gene shifts underpin enhanced nitrogen removal in a carrier-assisted transition from CANON to coupled CANON-denitrification - Neng-feng Qian; Shuai Zhang; Qi Luo; Qing-guo Chen; Ren-cun Jin; Li-juan Feng; Guang-feng Yang (Journal of Water Process Engineering, 2026)

Divergent activation of a glutathione-tryptophan module by cysteine and hydrogen sulfide enables metabolic recovery from cyanide poisoning in rice - Yi Kang; Xing-Hui Feng; Cheng-Zhi Li; Yu-Juan Lin; Xiao-Zhang Yu (Journal of Environmental Chemical Engineering, 2026)

Hyperspectral monitoring of wheat gluten index based on multi-model ensemble and adaptive learning - Shiyou Zhu; Juan Bai; Yulong Chen; Jingyu Chen; Caiyu Ji; Yingchao Hao; Sha Yang; Yu Zhao; Meijun Zhang; Meichen Feng; Wude Yang; Guangxin Li (Food Chemistry, 2026)

Recent advances in therapeutic agents for uranium poisoning: a comprehensive review - Juan Li; Wenrun Li; Feng Huang; Qiuchi Wang; Hongjia Liu; Liyi Chen; Qiuping Wang; Yong Li; Shiyan Fu; Yazhen Zhao; Yonghong Ran; Yuhui Hao (BioMetals, 2026)

Mapping quantitative trait loci (QTLs) for plant architecture traits using a high-density genetic linkage map in diploid potato (Solanum chacoense) - Tingyu Yin; Mengxin Ma; Min Yang; Mengting Ai; Juan Feng; Xiangyao Xiao; Fang Zhao; Canhui Li; Jing Yang (Genetic Resources and Crop Evolution, 2026)

Aquaculture-relevant florfenicol exposure causes hepatopancreatic bioaccumulation and metabolic-immune toxicity in the mud crab Scylla paramamosain - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Zhi-Long Chen; Xin-Jian Liu; Zhi-Xun Guo (Environmental Pollution, 2026)

Targeted isolation of previously undescribed fortunefuroic acid-type triterpenoids from Keteleeria pubescens using 1H NMR/LC-PDA-MS and assessment of ACL Inhibition - Chun-Jing Chi; Ze-Yu Zhao; Yi Zang; Cong Li; Jia Li; Dong Huang; Peng Sun; Juan Xiong; Yeun-Mun Choo; Jin-Feng Hu (Phytochemistry, 2026)

Collision-free path planning for underwater gliders in time-varying currents via dual-archive niching differential evolution - Zezhong Li; Rongshun Juan; Yang Li; Shoufu Liu; Tianshu Wang; Shuaikun Shi; Leihao Du; Wanjun Feng; Zhongke Gao (Ocean Engineering, 2026)

Corrigendum to “Metabolomics combined with machine learning reveals candidate metabolites and a putative working network associated with cereulide production in emetic Bacillus cereus” [Food Res. Int. 239 (2026) 119523] - Ying Feng; Minling Chen; Jiaxun Li; Keyuan Qin; Moutong Chen; Juan Wang; Qingping Wu; Yuting Shang; Yu Ding (Food Research International, 2026)

Metabolomics combined with machine learning reveals candidate metabolites and a putative working network associated with cereulide production in emetic Bacillus cereus - Ying Feng; Minling Chen; Jiaxun Li; Keyuan Qin; Moutong Chen; Juan Wang; Qingping Wu; Yuting Shang; Yu Ding (Food Research International, 2026)

Unraveling the fruity aroma in soy sauce aroma Baijiu by pinpointing key aroma compounds and evaluating their sensory impact - Yu-Jie Li; Xiao-Juan Zhang; Lan Wu; Zhen-Ming Lu; Lu-Qin Tian; Yun-Hao Lu; Li-Juan Chai; Hong-Yu Xu; Xiao-Long You; Yuan-Long Chi; Feng Hu; Zheng-Hong Xu (Food Chemistry, 2026)

Orbital engineering of Fe3C nanocluster decorated Fe single atom enables a superior oxygen reduction performance - Lu Liu; Daomeng Liu; Ziyi Feng; Peigen Liu; Jun Wang; Juan-Ding Xiao; Jia Yang; Junzhong Wang; Xifan Chen; Hongbao Li; Zhengkun Yang (Chemical Engineering Journal, 2026)

A simultaneous in-situ growth strategy to prepare CdS@SnO2 composites possessing high-density heterointerfaces for efficient U(VI) reduction - Zihui Wang; Ji-Ming Yu; Longfei Zhai; Haohao Li; Mengna Yan; Xi Feng; Rongfang Xu; Juan Ma; Wei-Wei Xiong (Chemical Engineering Journal, 2026)

Dual-responsive injectable hydrogel loaded with DPSCs accelerates diabetic wound healing by promoting mitochondrial transfer to reduce senescent cells - Yonghao Liu; Pengcheng Pang; Shangjin Feng; Wanyang Zhong; Juan Wang; Ye Liu; Xiaoyu Zheng; Ziwei Li; Heng Zhou; Yan He; Qingsong Ye (Chemical Engineering Journal, 2026)

Root system adaptation to heterogeneous habitats: divergent strategies and hierarchical plasticity in a clonal plant - Guangru Wang; Juan Wu; Pu Feng; Jiexuan Li; Siyu Mao; Jianmin Shi; Shebao Yu; Hongying Yu (Plant and Soil, 2026)

Retraction notice to “Global evapotranspiration from high-elevation mountains has decreased significantly at a rate of 3.923%/a over the last 22 years” [Sci. Total Environ. 931 (2024) 172804] - Yunying Wang; Zongxing Li; Qi Feng; Lanping Si; Juan Gui; Qiao Cui; Yue Zhao; Chong Xu (Science of The Total Environment, 2026)

Retraction notice to “Environmental effect and spatiotemporal pattern of stable isotopes in precipitation on the transition zone between the Tibetan Plateau and arid region” [Sci. Total Environ. 749 (2020) 141559] - Gui Juan; Zongxing Li; Feng Qi; Yuan Ruifeng; Ning Tingting; Zhang Baijuan; Xue Jian; Gao Wende; Nan Fusen; Ding Weixuan; Yang Anle; Liang Pengfei (Science of The Total Environment, 2026)

Catchment land use shapes lake-atmosphere thermal contrast and synchrony globally - Zhirong Yu; Gang Li; R. Iestyn Woolway; Jixiang Yang; Jiaming Hu; Juan Tao; Kun Shan; Kun Shi; Yunlin Zhang; Lian Feng; Erik Jeppesen; Qichao Zhou (Science Bulletin, 2026)

Genomic landscape of idiopathic male infertility and the pregnancy outcomes following assisted reproductive technology - Chen Tan; Tongyao Hu; Lanlan Meng; King Kin Lam; Qing Zhang; Xilin Xu; Shimin Yuan; Yurong Wang; Zilan Huang; Keren Zhou; Yong Li; Chunbo Xie; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Antihyperglycemic nor-chamigrane sesquiterpenoids from the fungus Antrodiella albocinnanmomea - Hui Liu; Jiaoxian Du; Hongfei Li; Weiwei Yu; Yu Liang; Juan He; Tao Feng (Phytochemistry, 2026)

Biochar increases plant biomass and reshapes biomass allocation through coordinated belowground and aboveground responses - Mei Yang; Jiahuan Guo; Juan Du; Lei Feng; Wenqiong Li; Mengke Huang; Hui Zhang; Huili Feng (Journal of Cleaner Production, 2026)

Effects of temperature changes on oxidative stress and mud crab reovirus (MCRV) replication in mud crab (Scylla paramamosain) - Guangxin Liu; Ganfeng Liu; Jianjun Jiang; Hongling Ma; Sigang Fan; Yiqin Deng; Changhong Cheng; Juan Feng; Shengkang Li; Zhendong Qin; Zhixun Guo (Fish & Shellfish Immunology, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Diverse plants recruit functional microbes as engines to drive ecosystem multifunctionality in post-fire forests - Hong-Rui Wang; Yu-Yang Liu; Yang Xu; Kai-Li Wang; Rui Deng; Fu-Juan Feng (Plant and Soil, 2026)

Evolution and functional characterization of the MdSKP8 gene as a conserved hub integrating hormone and antioxidant pathways for salt tolerance in apple - Miao Shao; Yongqing Feng; Shixiong Lu; Shangwen Yang; Jian Li; Xinyu Li; Zonghuan Ma; Guoping Liang; Baihong Chen; Juan Mao (Plant Cell Reports, 2026)

LncRNA MNX1-AS1 drives the progression of non-small cell lung cancer and serves as a ceRNA to target COMMD8 by sponging miR-218-5p - Gao-Feng Liu; Li Zhou; Yu-Bo Zhao; Jia-Hong Tang; Qing-Yuan Li; Xiao-Yong Ding; Xiao-Zhen Zhang; Su-Juan Cui; Yong Zhang; Zhen-Wei Sun (Journal of Molecular Histology, 2026)
The role and mechanistic action of MNX1-AS1 in non-small cell lung cancer (NSCLC) remain unclear. This study aimed to investigate the function of MNX1-AS1 in the progression of NSCLC. A total of 40 paired tumor and adjacent lung tissue samples from patients with NSCLC were collected to investigate the expression of MNX1-AS1. H1299 and HCC827 cells were transfected with sh-MNX1-AS1, shRNA-NC, miR-218-5p mimic, mimic-NC, pcDNA3.1-COMMD8, or empty vector (pcDNA3.1). The expression of MNX1-AS1, miR-218-5p, and COMMD8 was detected using quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using CCK-8 assays, while cell migration and invasion were evaluated using Transwell assays. Dual-luciferase reporter and RNA pull-down assays were performed to validate the targeting interactions between MNX1-AS1 and miR-218-5p, as well as between COMMD8 and miR-218-5p. In vivo, a nude mouse model was established: tumor volume and weight were measured after four weeks. Gene expression in tumor tissue was quantified using qRT-PCR, and Ki-67 expression was evaluated using immunohistochemistry. MNX1-AS1 expression was significantly upregulated in NSCLC tissues ( P < 0.05) and was correlated with poor prognosis in NSCLC patients. MNX1-AS1 knockdown markedly suppressed the viability, migration, and invasion of H1299 and HCC827 cells ( P < 0.05). Mechanistically, MNX1-AS1 acted as a molecular sponge for miR-218-5p, thereby relieving miR-218-5p-mediated repression of its direct target COMMD8 ( P < 0.05). Functional rescue experiments revealed that miR-218-5p silencing or COMMD8 overexpression partially reversed the inhibitory effects of MNX1-AS1 knockdown on the cell viability, migration, and invasion of H1299 and HCC827 cells. In vivo, sh-MNX1-AS1 significantly reduced tumor volume and weight ( P < 0.05). Moreover, the expression of MNX1-AS1, COMMD8, and Ki-67 were downregulated, while the expression of miR-218-5p was upregulated in sh-MNX1-AS1 tumor tissues ( P < 0.05). MNX1-AS1 promotes the progression of NSCLC by modulating the miR-218-5p/COMMD8 axis.

Combined toxicity and mechanism of cadmium and neonicotinoid insecticide to rice (Oryza sativa L.): reduced antioxidant defence mediated by flavonoid - Zhaoxia Fan; Na Liu; Fei Ge; Feng Li; Wenjun Zhou; Juan Gao (ENGINEERING Environment, 2026)

Effect of regional Hadley circulation–subtropical jet interaction: enhancement of the Central-Pacific ENSO teleconnection in the Southern Hemisphere - Weihan Ma; Juan Feng; Yujie Miao; Weiqi Wang; Xichen Li (Climate Dynamics, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Rockburst mitigation by microwave destressing in a deep drill-and-blast tunnel: thermal–damage–stress evolution with a slotted-wall coaxial applicator - Yuntan Ao; Xia-Ting Feng; Shiping Li; Xiaojun Zhang; Juan He; Tianyang Tong; Yifan Zhang; Feng Lin (Tunnelling and Underground Space Technology, 2026)

Fluid evolution and petroleum accumulation in the Middle Permian gas reservoirs of the Sichuan Basin, China - Yun Liao; Jianyong Zhang; Zeqi Li; Heng Wang; Juan Wu; Genshun Yao; Wenzheng Li; Feng Liang; Shugen Liu; Bin Deng (Journal of Asian Earth Sciences, 2026)

A Weight-Optimized Federated Learning Framework for Leak Detection in Water Distribution Networks - Juan Li; Weijia Feng; Xiaofeng Tang (Water Resources Management, 2026)

Erratum to: Fungal oxalic acid inhibits the deamidation of CERK1 ectodomain to dampen chitin-triggered plant immunity - Ben-Qiang Gong; Jun-Jie Liu; Juan Xu; Jiasen Cheng; Jian-Feng Li (Science China Life Sciences, 2026)

A new amide alkaloid from the coculture liquid cultures of two grape endophytic fungi Penicillium sp. YPT103-2 and Penicillium sp. YPT104 - Yu-Qin Yang; Jin-Feng Cao; Juan-Juan Pu; Dong-Ping Li; Chuan-Mao Zhang; Zhi-Jian Wu; Jian-Hai Ding (Natural Product Research, 2026)

STNMAE: Identifying Spatial Domains from Spatial Transcriptomics Data with Neighbor-Aware Multi-view Masked Graph Autoencoder - Qi Gao; Junliang Shang; Shasha Yuan; Feng Li; Juan Wang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

The interaction between inflammation and estrogen in adenomyosis : from molecular mechanisms to therapeutic strategies - Feng Li; Huai Jian Wang; Yu Zhang; Feng Juan Nan; Li Xu; Zhi Yong Liu; Wei Shi (Seminars in Immunopathology, 2026)
Adenomyosis is a common and difficult disease in gynecology. Its main clinical manifestations include uterine hypertrophy, excessive menstruation, pelvic pain and infertility, which have a serious impact on women’s health. Seriously affects women’s health. At present, the pathogenesis of this disease is not clear; however, the increase in local estrogen and the occurrence of an inflammatory response are widely believed to be closely related to the development of adenomyotic lesions. Although progress has been made in understanding how estrogen and inflammation play their respective roles in adenomyosis, the relationship between estrogen and inflammation and its impact on adenomyosis are not fully understood. In this work, we summarize the effects of estrogen and inflammation on the occurrence and development of adenomyosis, including the involved biological processes and related signal transduction mechanisms, as well as the targeted drugs for clinical treatment, and further summarize the interactions between the two in adenomyosis as well as the available evidence for clinical applications. This review helps to broaden our understanding of the role of the vicious inflammatory‒estrogen cycle in the pathogenesis and pathophysiology of adenomyosis, and it provides new ideas for the treatment of uterine adenomyosis. Graphical Abstract The vicious cycle of inflammation and estrogen promotes the development of adenomyosis.

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Four new cysteine derivatives with cytotoxic activity from Poecilobdella manillensis - Qingqing Fan; Peixing He; Hang Xiao; Juan He; Ting Wang; Zhenbei Lan; Feng Tian; Jianyuan Tang; Li Ma (Phytochemistry Letters, 2026)

UPLC-PDA-MS guided isolation of lindenane sesquiterpene oligomers with anti-neuroinflammatory activity from two rare Chloranthus species - Jun-Li Xin; Ke-Xin Li; Zhi-Xuan Wang; Xian-Neng Lu; Xue-Jiao Wang; Yi-Cheng Mao; Jin-Feng Hu; Juan Xiong (Phytochemistry, 2026)

Undescribed polyketides and alkaloids from the endophytic fungus Penicillium steckii HJT-A-10 - Dongliang Xiao; Xinge Yu; Junkai Qi; Xiaobao Li; Chuan Tang; Baomin Feng; Juan Guo; Xiaoyao Ma; Xuan Lu (Phytochemistry, 2026)

Phytochemical and biological studies on rare and endangered plants endemic to China. Part XLIX. Terpenoids and phenylpropanoid-substituted flavan-3-ols from the leaves of Camellia petelotii (golden-flower tea) and their bioactivities - Ze-Yu Zhao; Can Wang; Zhe-Lu Jiang; Jiang Wan; Juan Xiong; Yi Zang; Yeun-Mun Choo; Jia Li; Jin-Feng Hu (Phytochemistry, 2026)

Hydrolysis of beef sarcoplasmic protein by dry-aged beef-isolated Yarrowia galli and its flavor characteristics - Siyu Guo; Zhiqi Liu; Yujia Liu; Tingyu Li; Jian Feng; Baide Mu; Hongmei Li; Juan Wang; Guanhao Li; Chunxiang Piao (International Journal of Gastronomy and Food Science, 2026)

New strategy for high-value utilization of silver carp skin/bone mixture: Steam explosion combined with stepwise enzymatic hydrolysis to produce endogenous calcium-bound ACE inhibitory peptides - Zijuan Li; Qingxiang Feng; Yanlei Gao; Tao Yin; Juan You; Shanbai Xiong; Ru Liu (Innovative Food Science & Emerging Technologies, 2026)

Evaluation of Zanthoxylum bungeanum sprouts amino acids profile by capillary electrophoresis and principal component analysis - Chun-Mei Lv; Wen-Juan Shi; Xu-Kun Zhou; Wei-Feng Wang; Jun-Li Yang (Food Chemistry, 2026)

Structure–function relationships in chitosan films containing ZIF-8-confined Ligusticum jeholense essential oil: pH-triggered release and apple ring rot control - Xiao-Yi Tong; Yun-Feng Liu; Zhi-Hong Xu; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An; Fei Cao (Food Chemistry, 2026)

Efficient U(VI) reduction through the synergistic driving of electrostatic interactions and S-scheme heterojunctions - Haohao Li; Xi Feng; Chunhui Hou; Longfei Zhai; Juan Ma; Zihui Wang; Mengna Yan; Bing Zheng; Wei-Wei Xiong (Chemical Engineering Journal, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Synergistic Effects of El Niño–Southern Oscillation and Arctic Oscillation on the Winter Northern Hadley Circulation Edge - Xuan Liu; Juan Feng; Jianping Li (Advances in Atmospheric Sciences, 2026)

Stepwise Gradient in Fundamental Individualised Niche Differentiation Across Soil Microbiomes - Huaiqiang Liu; Juan Xu; Yihui Guo; Zhenyuan Lei; Na Wang; Wenya Wei; Liping Qu; Minchun Li; Yarong Feng; Wei Xie (Molecular Ecology, 2026)
Individual microbes often respond differently to the same environment, yet the magnitude of such niche variation inherent to individuals remains unresolved and is anticipated to differ substantially from community‐level average responses. We conducted metagenomic binning on monthly time‐series soil samples from three sites across seasonal cycles. By considering 440,571 genes as dimensions of the fundamental individualised niche (FIN), we traced FIN trajectories of archaea and bacteria during warming, cooling, and turning periods. We found that neither mean temperature nor temperature difference had a significant effect on FIN breadth or overlap. Instead, we discovered a temporally constant, stepwise gradient of niche differentiation across taxonomic categories. At the interdomain level (Archaea vs. Bacteria), niche overlap is approximately 25%, rising to ~40% at the interphylum level and ~60% at the interorder level. This discontinuous gradient likely marks the limit boundaries of niche variation, is closely linked to functional synergy within FINs, and provides a preliminary comparable ecological carrying capacity for each niche step, particularly regarding the interdomain balance.

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Dietary creatine supplementation promoted growth performance, muscle growth and protein deposition in red swamp crayfish (Procambarus clarkii) fed with all-plant-protein diets - Xinyuan Li; Changchun Song; Shouqi Xie; Min Wan; Yangyang Liu; Chenxi Wang; Guogen Su; Feng Huang; Juan Tian (Aquaculture, 2026)

Functional hyaluronic acid/gelatin hydrogel accelerates the closure and healing of diabetic wounds - Qianqian Du; Juan Liu; Chuanfeng Ding; Xiaofei Wang; Liangsheng Li; Qian Feng; Hao Tang; Qian Zhou; Yongsheng Yu (Carbohydrate Polymers, 2026)

Chaotic effects in completely autotrophic nitrogen removal over nitrite process: how minor dissolved oxygen variations reshape microbial community and functional genes to drive divergent nitrogen removal - Yue Li; Wei-jian Wang; Shuai Zhang; Qi Luo; Neng-feng Qian; Dong-zhi Chen; Ren-cun Jin; Li-juan Feng; Guang-feng Yang (Bioresource Technology, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Assessing NEX-GDDP-CMIP6 for extreme-temperature simulation in Northwest China and projecting changes under SSP-based scenarios - Qian Li; Tongfei Zhang; Shuang Wang; Xiaohua Fu; Long Cheng; Pan Wang; Juan Feng (Climate Dynamics, 2026)

Sox9a and amh indirectly cooperate to promote spermatogonia differentiation and gonadal development in Cyprinus carpio var. koi(koi carp) - Xinglei Wang; Wenchao Liu; Bo Zheng; Yuming Zhao; Fengjie Guo; Juan Li; Feng Wang (Animal Reproduction Science, 2026)

Study on S-wave Velocity Structure and Seismogenic Structure in the Source Region of the 1976 M6.2 Horinger Earthquake - Dong-yang Pei; Xiao-ming Han; Juan Li; Fan Zhang; Li-feng Chen; Shu-bo Wang; Wei Guo; Xin Wang; Tie-suo Zhao; Xing Zhao; Jin-zhe Bao (Applied Geophysics, 2026)

Multifaceted regulation of immune cells in radiation-induced pulmonary fibrosis: from mechanistic insights to targeted therapies - Li Shen; Wanrong Zhang; Yonghao Yang; Zhiqiang Du; Shiyan Fu; Feng Huang; Xiaoyu Yang; Juan Li; Yonghong Ran; Yuhui Hao (Inflammation Research, 2026)

A novel salt-tolerant purple photosynthetic bacterium Afifella marina TC201-1 for sustainable treatment of saline aquaculture wastewater - Shuai Liang; Kai-Hua Geng; Ding-xian Xu; Ya-Juan Wang; Wei-Yu Du; Yun-Feng Liu; Ya-Nan Lu; Li Wang; Yuan Wang; Jing Gu; Yu-Ting Cong; Lian-Shun Wang; et al. (Journal of Water Process Engineering, 2026)

In-situ construction of novel dual bismuth–rich Bi4O5Br2/Bi7O9I3 S-scheme heterojunction with enhanced photocatalytic activity for degradation of diverse persistent organic pollutants - Jia-Lin Zong; Hui-Long Wang; Hao Huang; Yi-Hui Zhao; Li-Juan Han; Wen-Feng Jiang (Journal of Environmental Chemical Engineering, 2026)

A novel antioxidant peptide DD12 (DWPDARGIWHND) derived from dry cured ham alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-ARE pathway - Ying-dao Nan; Si-qi Chen; Guan-hao Li; Ting-yu Li; Bai-de Mu; Juan Wang; Jian Feng; Hong-mei Li; Chun-xiang Piao (Food Research International, 2026)

Multi-target antidiabetic peptides from highland barley (Qingke): Identification, molecular docking, and inhibitory mechanisms against α-amylase, α-glucosidase, and DPP-IV - Juan Li; Muyan Ma; Feng Liang; Yan Du; Wenju Zhou; Pin Ma; Falin Zhang; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li (Food Chemistry, 2026)

Size-dependent performance and adaptive mechanisms of anammox granular sludge under fluctuating low-temperature conditions - Guang-feng Yang; Qi Luo; Neng-feng Qian; Ben-ze Chang; Ya-lei Liu; Dong-zhi Chen; Li-juan Feng (Biodegradation, 2026)

Polyketides and drimane sesquiterpenoids from kiwi plant endophytic fungus Aspergillus flavus J302-03 with antibacterial and anti-inflammatory activities - Xin-Wen Luo; Fang-Lu Wei; Hong-Fei Li; Jin-Yao Mao; Yan-Ling Yang; Juan He; Tao Feng (Phytochemistry, 2026)

Microwave-assisted extraction enhances the epicatechin and bovine serum albumin the interaction by inducing protein conformational changes - Wen-Ting Duan; Jiang-Feng Yuan; Li-Juan Wang; Meng-Xue Sun; Xiao-Wen Yang; Zhi-Jun Qiu (Food Chemistry, 2026)

Complementary strengths of eDNA and morphology in assessing chemical stress on freshwater plankton communities: Evidence from mesocosm experiments - Kai-Sheng Yao; Paul J. Van den Brink; Lu-Kai Qiao; Pei-Liang Zhou; Li-Juan Tan; Feng-Jiao Peng; Guang-Guo Ying (Environmental Pollution, 2026)

The Time Reliable Effect of Probiotic Clostridium butyricum on the Growth of Spotted Sea Bass (Lateolabrax maculatus) - Yiqin Deng; Liwen Xu; Keng Yang; Ziyang Lin; Shujun Zang; Kui Jiang; Wangdong Li; Nabil A. Ibrahim; Hongling Ma; Changhong Cheng; Juan Feng (Probiotics and Antimicrobial Proteins, 2026)

Optimizing hybrid breeding in Roscoea: heterosis and inheritance patterns with R. cautleoides as a key parent - Yuan-Yue Zhang; Ming-Chao Chen; Yi-Guo Li; Feng-Juan Mou (Euphytica, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Moderate drought stress followed by re-watering enhances wheat starch biosynthesis, improving granule size distribution and physicochemical properties - Jialu Wen; Jingyi Feng; Jianfeng Yao; Jianke Xiao; Vinay Nangia; Juan Li; Yang Liu (Carbohydrate Polymers, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Deep Subdomain Adaptation Network for Three-Dimensional Mineral Prospectivity Modeling with Imbalanced Data: A Case Study of the Damiao–Hongshila Fe–V–Ti Belt, China - Zhiqiang Zhang; Wenliang Chen; Emmanuel John M. Carranza; Wei Han; Xinxing Liu; Yingjie Li; Juan Zhang; Feng Li; Ziyang Lu; Yongjun Su; Gongwen Wang (Natural Resources Research, 2026)

Immunotherapy checkpoint inhibitor-combination therapy versus chemotherapy alone among Chinese population in cholangiocarcinoma treatment: a systematic review and meta-analysis - Li Shi; Wei Du; Juan Miao; Xi-Yuan Peng; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Si-Qi Gao; Hong-Lin Chen (European Journal of Clinical Pharmacology, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Petrographic, Mineralogical and Geochemical Constraints on the Origin of Regional-Scale Dolomitization: A Case Study of the Cambrian–Lower Ordovician Dolomites in the Bachu Area, Central Tarim Basin, China - Miao Li; Yushuang Zhou; Yongqiang Zhao; Juan Xu; Fei Wu; Feng Geng (Journal of Earth Science, 2026)

Depleted uranium exposure induced ferroptosis in renal cells via the ETHE1/P38-MAPK pathway - Feng Huang; Wenrun Li; Juan Li; Yonghong Ran; Shiyan Fu; Li Shen; Qi Li; Xiaoyu Yang; Yazhen Zhao; Yuhui Hao (Archives of Toxicology, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Mud crab reovirus infection disrupts the intestinal microbiota and intestinal physiological homeostasis in mud crabs (Scylla paramamosain) - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2026)

Ceritinib–ibuprofen synergistic hepatotoxicity: Insights from real-world data and liver organoid models - Shiyi Tan; Yun Yang; Li Ma; Xulei Zuo; Jianhua Rao; Yuepu Pu; Feng Cheng; Zhongze Gu; Juan Zhang (Toxicology, 2026)

Cytochalasans from the fungus Chaetomium globosum with cytotoxic activities against HepG2 cell line - Hong-Fei Li; Tian Jin; Jiao-Xian Du; Xin-Wen Luo; Guo Zhang; Wang-Qiu Deng; Juan He; Tao Feng (Phytochemistry, 2026)

Impact of preceding winter ENSO on the following spring Hadley circulation edge - Xuan Liu; Juan Feng; Jiaxin Li (Atmospheric Research, 2026)

Retraction Note to: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2026)

Carbon dot-enhanced nanobody-based fluorescence immunoassay for ultrasensitive Listeria monocytogenes detection in dairy products - Xuan Liu; Shurong Li; Juan Wei; Xueyi Fan; Kai Zheng; Qinkai Yang; Xiaohui Du; Ruixue Feng; Peixiang Wang; Jianlong Wang; Yanru Wang (Analytica Chimica Acta, 2026)

A three-dimensional coupling evaluation model for carbon source-sink in riparian zones - Na Li; Juan Peng; Feng Yan (Journal of Hydrology, 2025)

Joint influences of ENSO and East Asian winter monsoon on the Hadley circulation in the Asian monsoon domain - Mengying Du; Yan Li; Juan Feng; Qi Wen; Wenjun Song; Zhilan Wang (Global and Planetary Change, 2025)

Identification of key metabolites in fermented quinoa and their α-glucosidase inhibitory mechanisms using widely targeted metabolomics and molecular simulation - Li Zhao; Juan Liao; Haijiao Zhao; Cuiping Feng (Food Chemistry, 2025)

Unraveling cross-variations in fruit aroma and color during ‘Red Delicious’ bud sport: Insights from targeted metabolomics and transcriptomics - Miao Shao; Yongqing Feng; Shangwen Yang; Huimin Gou; Xin Li; Zonghuan Ma; Guoping Liang; Baihong Chen; Juan Mao (Food Chemistry, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Microfluidic engineering of AgNPs@ZIF-8 composites enables tunable peroxidase-like catalytic activity for enhanced bacterial inactivation - Chong Hu; Juan Tao; Liqiang Zhang; Jiancheng Zha; Panpan Cui; Yanbao Li; Yuan Zhou; Jing Su; Feng Liu; Liangjun Li (Chemical Engineering Journal, 2025)

Anion-trapping polyhedral oligomeric silsesquioxane cage structures to modify interfacial architecture for exceptional multifunctional coatings - Kangwei Gongsun; Zhuyin Gang; Xiang Gao; Juan Qiu; Kanglu Feng; Chunchao Chen; Changming Bu; Xiaofan Li; Houyi Ma (Chemical Engineering Journal, 2025)

Synthesis of d-p orbital hybridised ultra-thin high-entropy oxide nanosheets for efficient oxygen evolution reaction - Xiaoyin Li; Chuncheng Xu; Lulu Suo; Juan Wang; Deliang Zhang; Miaomiao Xing; Shuhua Lv; Hongyu Mou; Qingjia Liu; Dongrun Li; Lei Feng; Debao Wang; et al. (Chemical Engineering Journal, 2025)

Fungal oxalic acid inhibits the deamidation of CERK1 ectodomain to dampen chitin-triggered plant immunity - Ben-Qiang Gong; Jun-Jie Liu; Juan Xu; Jiasen Cheng; Jian-Feng Li (Science China Life Sciences, 2025)

The role of succinylation-mediated metabolic reprogramming in tumor progression - Siyi He; Chunduo Wang; Ranran Li; Kexin Xu; Wuzhiyi Zhang; Binbin Feng; Shengtao Cheng; Jihua Ren; Juan Chen (Molecular Biology Reports, 2025)

Proteomics revealed the underlying mechanism of STAT1-induced cognitive deficits in 2-month-old C57 mice - Xiao Li; Ting Li; Bocheng Xiong; Juan Luo; Xifei Yang; Yan Feng (Experimental Brain Research, 2025)

Summer PM2.5 concentrations in the northern subtropics modulated by the Hadley circulation edge location - Shuang Wang; Juan Feng; Sijia Lou; Jianping Li; Xuanliang Ji; Falei Xu (Climate Dynamics, 2025)

Integrated Geology-Geophysics Exploration of Rare Metal Deposits in the Yidun Island Arc Collisional Orogen - Rong Yang; Yu Peng; Li Qing; Qian-kun Liu; Xue-feng Hao; Han Wu; Jun-bo Fan; Hong-juan Chen; Tao Yang (Applied Geophysics, 2025)

Inversion of the Deep Structure of the Northern Margin of the Ordos Block Using Teleseismic Receiver Functions and Gravity Data - Feng-Zhi Cui; Fan Zhang; Juan Li; Dong-Yang Pei; Yi-Hang Bai; Lei Wang; Hui Wang (Applied Geophysics, 2025)

ESM-YOLOv11: A lightweight deep learning framework for real-time peanut leaf spot disease detection and precision severity quantification in field conditions - Yapeng Zhang; Juan Liu; Shangzhou Li; Sifan Feng; Ziqi Sun; Yanan Cui; Haijiao Liu; Juanjuan Zhang; Fernando Auat Cheein; Wei Guo (Computers and Electronics in Agriculture, 2025)

Chromosome-level genome of Nardostachys jatamansi and comparative genomics analysis reveals its sesquiterpenoid biosynthesis - Xuexue Li; Yuan Liu; Xuan Liu; Huachun Sheng; Juan Li; Wenbing Li; Ying Li; Chen Chen; Jingqiu Feng; Xinjia Yan; Zhengming Yang; Yanfei Huang; et al. (Phytochemistry, 2025)

Discovery of ca. 2.33–2.22 Ga magmatic activities in the Longshan Complex bordering the southwestern margin of the North China Craton: Implications for tectonic transformation - Yi-Yi Zhang; Jun-Sheng Lu; Rui-Ying Zhang; Yu-Ting Li; Xu Kong; Gang Liu; Qiang Feng; Zeng-Yin Duan; Juan-Juan Li (Lithos, 2025)

Synthesis and antitumor evaluation of oleanolic acid acylhydrazone derivatives - Juan Cai; Bo-Wen Pan; Liang-Liang Zheng; You-Ping Tian; Zhang-Chao Dong; Li-Juan Liu; Ting-Ting Feng; Ying Zhou; Xiong-Wei Liu; Yang Shi (Molecular Diversity, 2025)

June persistence barrier of tropical land precipitation - Ran An; Jianping Li; Juan Feng (Climate Dynamics, 2025)

Isolation and Genomic Characterisation of Lymphocystivirus platichthys1 in Brackish‐Water Cultured Spotted Seabass Lateolabrax maculatus in Zhuhai, South China - Hongling Ma; Changhong Cheng; Yiqin Deng; Zhixun Guo; Yong Li; Guangxin Liu; Huajian Lin; Liwen Xu; Juan Feng (Journal of Fish Diseases, 2025)
Lymphocystis disease virus (LCDV) stands as one of the most widespread causative agents affecting a diverse array of teleost globally. According to the literature, LCDV encompasses four species, and Lymphocystivirus paralichthys1 (known as LCDV‐C) has long been regarded as the predominant national epidemic isolate in mainland China. In this study, two instances of severe mass mortalities associated with LCDV in brackish‐water cultured juvenile spotted seabass in Zhuhai, South China, were monitored starting from early April 2023. The death toll in these two cases peaked at approximately 4000 and 10,000 fish per day, respectively, with cumulative mortalities reaching around 70% within 19 days of the disease outbreak. Based on clinical symptoms, histopathological analyses and transmission electron microscopy observations, the diseases were diagnosed as LCDV infections. The virus was isolated using the Mandarin fish fry (MFF‐1) cell line and named LCDV‐ZH04/23. Subsequently, LCDV‐ZH04/23 was roughly purified, and its entire genome was sequenced and annotated. The results indicated that ZH04/23 consists of 102,661 base pairs, encodes 108 putative viral genes and has a G/C content of 29.3%. Genomic collinearity analysis revealed that the whole genome of ZH04/23 exhibits the highest similarity (99.9%) to the well‐known Lymphocystivirus platichthys1 (LCDV‐1) from Europe, but shows significant divergence from the other three LCDV species. Collectively, this study marks the first isolation and characterisation of L. platichthys1 at the whole genome level from cases of severe mass mortalities in pond‐cultured spotted seabass in China. Moreover, it is the first to identify L. platichthys1 as an emerging pathogen in cultured spotted seabass.

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

High efficacy of (Z)-ligustilide in inhibiting postharvest apple ring rot and its antifungal mechanism against Botryosphaeria dothidea - Xiao-Yi Tong; Li-Li Song; Hui-Fang Du; Ya-Hui Zhang; Jia-Wen Shou; Cai-Juan Zheng; Wen-Bin Gao; Zhong-Cheng Liu; Du-Qiang Luo; Yun-Feng Liu; Fei Cao (Postharvest Biology and Technology, 2025)

Evolution of global O3-NOx-VOCs sensitivity before and after the COVID-19 from the ratio of formaldehyde to NO2 from satellite observations - Dakang Wang; Dongchuan Pu; Isabelle De Smedt; Lei Zhu; Xiankun Yang; Wenfu Sun; Hui Xia; Zhaolong Song; Xicheng Li; Juan Li; Aoxing Zhang; Xu Feng; et al. (Journal of Environmental Sciences, 2025)

Chemical constituents from the stems of Daphniphyllum angustifolium Hutch. and their chemotaxonomic significance - Xiao-Juan Huang; Heng-Gang Zhang; Xiao-Hong Li; Yu-Bin Wei; Khalid-Hassan Mohamed; Chang-Qin Yin; Hao-Fei Yu; Cai-Feng Ding; Lan-Chun Zhang (Biochemical Systematics and Ecology, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Factors Controlling Precipitation Stable Isotopes in Qinghai-Tibet Plateau Transitional Area, China - Zongjie Li; Bin Xu; Hao Li; Qi Feng; Xiaoying Liu; Mengqing Liu; Juan Gui; Jian Xue (Chinese Geographical Science, 2025)

Regional Perspective of Hadley Circulation and Its Uncertainties among Different Datasets: Biases of ENSO-Related Hadley Circulation in CMIP Models - Wenzhu Wang; Juan Feng; Yadi Li; Yujie Miao; Xichen Li (Advances in Atmospheric Sciences, 2025)

Diterpene-phenylpropanoid hybrids and structurally diverse diterpenoid monomers from the endangered conifer Podocarpus annamiensis and their bioactivities - Chi Song; Ze-Yu Zhao; Yi Zang; Jia Li; Yeun-Mun Choo; Haibo Wang; Guangyao Mei; Juan Xiong; Jin-Feng Hu (Phytochemistry, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

Environmental levels of bis(2-ethylhexyl)-tetrabromophthalate (TBPH) cause thyroid toxicity and early carcinogenic signals in juvenile fish - Xiang-sheng Hong; Liang Yan; Wei Sang; Wang Liu; Zhi-tong Li; Juan Wang; Sai-hong Yan; Jia-jing Xin; Gao-feng Zhao; Xu-fa Ma; Jin-miao Zha (Environmental Pollution, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

A novel integrated gasification fuel cell with carbon capture and storage (IGFC/CCS) based on synergistic energy gradient utilization and techno-economic optimization - Jingwei Li; Rongrong Zhai; Lingjie Feng; Yutong Wang; Juan Xu (Chemical Engineering Journal, 2025)

Engineered macrophage-targeted germacrone-bearing nanosheet achieves synergistic treatment of acute kidney injury through macrophage polarization modulation and oxidative stress alleviation - Yunguang Wang; Shaoting Wang; Qikai Luo; Yourou Zhou; Xingchen Li; Yiwei Shang; HuaiYu Wang; Egor Y. Plotnikov; Xinyu Liao; Wei Feng; Qiang He; Juan Jin (Chemical Engineering Journal, 2025)

Soil water sources and transport modes based on stable isotope tracing in Northeastern Qinghai-Tibet Plateau - Juan Gui; Youjing Yuan; Zongxing Li; Qi Feng; Fa Du (Journal of Mountain Science, 2025)

Novel L1A/C RFLP 1–3-4 porcine reproductive and respiratory syndrome virus causing severe intestinal infections in China - Bo Han; Yi-han Lu; Jiu-ying Sun; Xin-lei Li; Wen-juan Zhang; Xiao-xue Yu; Gang Xu; Dao-wen Li; Xue-jiao Cheng; Chun-xue You; Ying-Feng Sun (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Diaporolide, a new 10-membered lactone derivative from the endophytic Diaporthe sp. RYF-Br-5 associated with the rare conifer Keteleeria pubescens - Li-Hong Yan; Hao-Wei Chen; Peng Hu; Jiyang Li; Juan Xiong; Ze-Xin Jin; Jin-Feng Hu (Phytochemistry Letters, 2025)

Structural design and solid electrolyte interphase modulation of SiOC-based anodes via N-doping for fast-charging lithium-ion batteries - Juan Wang; Yaqian Li; Siwen Jin; Xiuhui Zheng; Juncong Yuan; Debin Kong; Han Hu; Xiang Feng; De Chen (Chemical Engineering Journal, 2025)

Reassessing the ENSO-related Hadley circulation contraction from a regional perspective - Yujie Miao; Tao Lian; Juan Feng; Yadi Li; Wenzhu Wang; Yurong Hou; Xichen Li (Atmospheric Research, 2025)

Asymmetric impacts of the preceding winter Western Pacific Hadley circulation on adjacent tropical cyclone frequency - Falei Xu; Juan Feng; Yan Li; Zhilan Wang (Climate Dynamics, 2025)

Phytochemical and biological studies on rare and endangered plants endemic to China. Part XLIV. Integrated NMR/EI-MS/LC-PDA-ESIMS approach for dereplication and targeted isolation of fortunefuroic acids from Keteleeria fortunei across diverse geographical origins - Ze-Yu Zhao; Zhe-Lu Jiang; Ying-Peng Tong; Chun-Jing Chi; Yi Zang; Yeun-Mun Choo; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

Antibiotic-induced multi-trophic effects and their cascades in a sub-tropical freshwater ecosystem - Kai-Sheng Yao; Pei-Liang Zhou; Li-Juan Tan; Hua-Qiao Yang; Lu-Kai Qiao; Fang-Zhou Gao; You-Sheng Liu; Feng-Jiao Peng; Guang-Guo Ying; Paul J. Van den Brink (Journal of Hazardous Materials, 2025)

Recent innovations in Grifola frondosa polysaccharides: production, properties, and their biological activity - Umar Zeb; Tariq Aziz; Wen-Jing Sun; Abdul Haleem; Guo-Qiang Guan; Li-Juan Meng; Lei Sun; Feng-Jie Cui (Food Bioscience, 2025)

Unravelling the pathogenesis of Vibrio parahaemolyticus infection: impacts on antioxidant and innate immunity gene responses in Scylla paramamosain - Guangxin Liu; Ce Li; Sigang Fan; Hongling Ma; Yiqin Deng; Jianjun Jiang; Changhong Cheng; Juan Feng; Li Lin; Zhendong Qin; Zhixun Guo (Fish & Shellfish Immunology, 2025)

Comparative analysis of the effects of different dimensionality reduction algorithms on hyperspectral estimation of total nitrogen content in wheat soils - Juan Bai; Shiyou Zhu; Yingchao Hao; Xinzhe Li; Chenbo Yang; Chao Wang; Xingxing Qiao; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Sha Yang; et al. (European Journal of Agronomy, 2025)

Stress-relieved synergistic structure engineering achieving robust monolithic porous silicene sheets from micro-sized siloxene for high-rate and high-energy lithium-ion batteries - Juan Geng; Hengtao Shen; Zhengran Wang; Zhiwei Ni; Chuanliang Wei; Yuan Li; Kangdong Tian; Xinlu Zhang; Shenglin Xiong; Jinkui Feng (Chemical Engineering Journal, 2025)

Delineation of polymetamorphism from the middle-low-grade metamorphic complex in the Dengfeng area, southern North China Craton, resolved by multiple mineral petrochronology and phase equilibrium modelling - Qiang Feng; Jun-Sheng Lu; Xu Kong; Gang Liu; Yu-Ting Li; Yi-Yi Zhang; Zeng-Yin Duan; Juan-Juan Li (Precambrian Research, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Corrigendum to “A highly sensitive and reusable magnetic nano-electrochemical biosensor for the detection of the liver cancer biomarker heat shock protein 70” [Chem. Eng. J. 505 (2025) 159860] - Ruming Liu; Ying Li; Yan Liu; Yixuan Wang; Qiuyue Si; Dorothy Araba Yakoba Agyapong; Juan Feng; Ruiqin Fang; Lixia Tang; Fei Cao; Hongjuan Zeng (Chemical Engineering Journal, 2025)

The mouse resource at National Resource Center for Mutant Mice of China - Bingzhou Han; Dongshen Chen; Zhong Chen; Ting Wang; Kaiyuan Zi; Rui Feng; Xiaoliu Yang; Ling’en Li; Juan Liang; Xiang Gao (Mammalian Genome, 2025)

Determination of the spatiotemporal evolution patterns and obstacle factors of coupling coordination of the water–energy–food–ecology system in Ordos City, China - Jihong Qu; Jixian Lin; Mengting Cheng; Zezhong Zhang; Kai Feng; Fei Wang; Kun Ren; Juan Zhou; Yanbin Li (Environmental Geochemistry and Health, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

Adaptive changes of biofilm and sludge in CANON process under various organics stresses: Performance, biomass characteristics and metabolic pathways - Ben-ze Chang; Yi-chun Zhao; Shuai Zhang; Qi Luo; Dong-zhi Chen; Ren-cun Jin; Li-juan Feng; Guang-feng Yang (Process Safety and Environmental Protection, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Nb2CTx modulated glycine film with multi-orientational piezoelectricity and photothermal functions designed for biomedical applications - Weiying Zheng; Tong Li; Lili Qian; Juan Ma; Zhibo Liu; Fei Jin; Zhidong Wei; Ting Wang; Zhang-Qi Feng (Chemical Engineering Journal, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Dynamic effects of Aeromonas sobria infection on intestinal morphology, microbiota and goblet cells of rainbow trout (Oncorhynchus mykiss) - Li-Ping Liu; Peng-Tian Kang; Feng-Yuan Ding; Dong-Hong Shao; Bao-Shan Wang; Juan Yang; Wen-Hui Gao; Wang-Dong Zhang; Wen-Hui Wang; Ji-Xing Liu (Aquaculture, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Sesquiterpenoids from Inula britannica and their potential mechanism for immunomodulation - Hui-Lin Zhang; Na Wang; Xu-Liu Shi; Miao-Miao Wang; Qi-Meng Zhu; Jing Chang; Yan-Li Feng; Juan Zhang; Feng Qiu; Cheng-Peng Sun (Phytochemistry, 2025)

Genomic, transcriptomic, and metabolomic analyses reveal convergent evolution of oxime biosynthesis in Darwin’s orchid - Kai Jiang; Birger Lindberg Møller; Shaofan Luo; Yu Yang; David R. Nelson; Elizabeth Heather Jakobsen Neilson; Joachim Møller Christensen; Kai Hua; Chao Hu; Xinhua Zeng; Mohammed Saddik Motawie; Tao Wan; et al. (Molecular Plant, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Covalent triazine based organic polymers modified ionization source for rapid and sensitive analysis of phytoestrogens - Yu Bian; Bo Nie; Tong Liu; Xiu-Juan Wang; Xiu-Li Xu; Xiao-Yan Pei; Jian He; Li Li; Feng Zhang (Food Chemistry, 2025)

Epigenetic nanoplatform for synergistic immune activation and immunogenicity restoration enhancing cancer radio-immunotherapy - Zhenhu He; Xiaopei Peng; Jiong Li; Yaning Zhu; Xuan Zhang; Junhong Duan; Jing Ni; Mengtian Ma; Juan Wang; Zhenguo Liu; Bin Feng; Wenbin Zeng; et al. (Chemical Engineering Journal, 2025)

17β-Trenbolone Exposure Enhances Muscle Activity and Exacerbates Parkinson’s Disease Progression in Male Mice - Xiang Zuo; Hui-Juan Bai; Qi-Li Zhao; Shu-Hui Zhang; Xin Zhao; Xi-Zeng Feng (Molecular Neurobiology, 2025)

Recirculating aquaculture mode has high sustainability and environmental accommodation capacity via better energy-saving and water-saving effects in Cynoglossus semilaevis production - Feng Wang; Xiao Mei; Bo Liu; YuMing Zhao; Juan Li; WenSheng Li; Shiyong Chen (Aquaculture, 2025)

Cadmium induces spontaneous abortion by impairing endometrial stromal cell decidualization - Xue-Ke Zhang; Xuan Li; Xing-Xing Han; Dong-Ying Sun; Yu-Qin Wang; Zi-Zhuo Cao; Lu Liu; Zi-Han Meng; Guo-Jing Li; Yu-Jie Dong; Dan-Yang Li; Xiao-Qing Peng; et al. (Toxicology, 2025)

Association between air temperature exposure and childhood rhinitis risk, and the mediating role of ambient O3: A multi-city study of 40,103 Chinese preschool children - Zhiping Niu; Ling Zhang; Xin Zhang; Chan Lu; Tingting Wang; Xiaohong Zheng; Dan Norback; Juan Wang; Yanyi Xu; Jing Wei; Feng Li; Li Peng; et al. (Sustainable Cities and Society, 2025)

Bioactivity-guided isolation of potent inflammasome and mitochondria damage inhibitory diterpenoids from Orthosiphon wulfenioides - Wen-Chao Tu; Peng-Yun Yang; Xing-Jie Zhang; Yuan-Lin Kong; Bo Li; Hui-Juan Wang; Muhammad Aurang Zeb; Xiao-Li Li; Mei-Feng Liu; Wei-Lie Xiao (Phytochemistry, 2025)

Structure-rheological relationship of capillary protein oleogels: The role of particle wettability - Gao-Shang Wang; Long-Yuan Zhang; Guang-Xin Feng; Chuan-Wu Han; Li-Juan Wang; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2025)

The variation of soil water content and its driving factors in different melting periods in the Three River Headwaters Region: A implication for vegetation restoration - Zongxing Li; Qiao Cui; Qi Feng; Bin Qiao; Juan Gui (Ecological Engineering, 2025)

A highly sensitive and reusable magnetic nano-electrochemical biosensor for the detection of the liver cancer biomarker heat shock protein 70 - Ruming Liu; Ying Li; Yan Liu; Yixuan Wang; Qiuyue Si; Dorothy Araba Yakoba Agyapong; Juan Feng; Ruiqin Fang; Lixia Tang; Fei Cao; Hongjuan Zeng (Chemical Engineering Journal, 2025)

Grevillosides R-S: glucosides of 5-alkylresorcinol derivatives from roots of Ardisia crispa (Thunb.) A. DC - Xing-xiang Long; Shuang Zhang; Li-juan Xiang; Rui-hang Hu; Ting-ting Feng; Ying Zhou; Xin Yin (Natural Product Research, 2025)

Exposure to outdoor humid-heat and indoor dampness-mold during infancy is associated with increased childhood asthma risk: A large-scale multi-city study in Chinese preschool children - Zhiping Niu; TianYi Chen; Ling Zhang; Xin Zhang; Chan Lu; Tingting Wang; Xiaohong Zheng; Dan Norback; Juan Wang; Yanyi Xu; Feng Li; Li Peng; et al. (Sustainable Cities and Society, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

Targeted isolation of lignans from the roots of Anthriscus sylvestris (L.) Hoffm. by small molecule accurate recognition technology - Yan-ling Liu; Yan-gang Cao; Ya-juan Zheng; Ying Niu; Lan Chen; Xu Chen; Xin-yi Ma; Xiang-da Li; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Prevalence and genomic characteristics of becAB-carrying Clostridium perfringens strains - Mingjin Fang; Yuan Yuan; Edward M. Fox; Ke Wu; Xin Tian; Likun Zhang; Hang Feng; Ruichao Li; Li Bai; Xinglong Wang; Zengqi Yang; Rong Zhang; et al. (Food Microbiology, 2025)

Research progress of chlorine corrosion resistance in seawater electrolysis: Materials and technologies - Li-Juan Yang; Hao-Yue Guan; Shuo Yuan; Tao Sun; An-Ning Jiang; Ji-Jun Feng (Chemical Engineering Journal, 2025)

Activation of protein kinase B rescues against thapsigargin-elicited cardiac dysfunction through regulation of NADPH oxidase and ferroptosis - Xiaohu Wang; Feng-Juan Li; Yong Cheng; Shuying Chen; Shuyi Zhu; Yingmei Zhang; Russel J. Reiter; Milad Ashrafizadeh; Jie Lin; Guizhen Wang; Ling Lin; Jun Ren (Chemico-Biological Interactions, 2025)

DET1 modulates ATAF1-repressed thermosensory elongation through ubiquitination in Arabidopsis - Shuai Yuan; Yan Li; Yayi Li; Juan Wei; Min Liu; Feng Yang; Xiuhong Yao (Plant Cell Reports, 2025)

Joint influences of the PDO and AMV on the linkage between tropical SST and Hadley Circulation - Jiaxin Li; Juan Feng; Xuan Liu (Climate Dynamics, 2025)

A novel ATP2A2 mutation in Darier and genotype phenotype: correlation analysis - Xiaofen Guo; Juan Du; Mingwei Lv; Yi Hu; Qi Zhen; Weiwei Chen; Yirui Wang; Zhuo Li; Chunmeng Liu; Xinyu Feng; Wanli Niu; Yu Zhang; et al. (Genes & Genomics, 2025)

Editorial: Endocrine regulation and physiological adaptation of stress response in aquatic organisms, volume II - Yi-Feng Li; Yiming Li; Marco António Campinho; Juan Fuentes (Frontiers in Marine Science, 2024)

Major specialized natural products from the endangered plant Heptacodium miconioides, potential medicinal uses and insights into its longstanding unresolved systematic classification - Ze-Yu Zhao; Jiang Wan; Hao-Wei Chen; Zhong-Shuai Sun; Yu-Tian Tao; Yingpeng Tong; Yi Zang; Yeun-Mun Choo; Pan Wang; Yue-Ling Li; Chun-Xiao Jiang; Junming Li; et al. (Phytochemistry, 2024)

A Protocol for Body MRI/CT and Extraction of Imaging-Derived Phenotypes (IDPs) from the China Phenobank Project - Chengyan Wang; Shuo Wang; Sha Hua; Ruokun Li; Yan Li; Zhang Shi; Kai Feng; Lizhen Lan; Meng Liu; Xutong Kuang; Xueqin Xia; Shihai Zhao; et al. (Phenomics, 2024)

Molecular cloning and gene expression of acc2 from grass carp (Ctenopharyngodon idella) and the regulation of glucose metabolism by ACCs inhibitor - Manxia Cao; Xinyuan Li; Lixue Dong; Hua Wen; Ming Jiang; Xing Lu; Feng Huang; Juan Tian (Molecular Biology Reports, 2024)

Competitive adsorption of polycyclic aromatic hydrocarbons on phosphorus tailing-modified sludge biochar provides mechanistic insights - Anrong Liu; Li-Juan Feng; Yangyang Ou; Xiaoya Zhang; Jinhong Zhang; Hongyan Chen (Environmental Geochemistry and Health, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Transcriptome analysis of Scylla paramamosain hepatopancreas response to mud crab dicistrovirus-1 infection - Min-Ze Liao; Chang-Hong Cheng; Gui-Ying Li; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Jian-Jun Jiang; Juan Feng; Zhi-Xun Guo (Fish & Shellfish Immunology, 2024)

Understanding the mechanisms and potential pathways of soil carbon sequestration from the biogeochemistry perspective - Xiaojuan Feng; Guohua Dai; Ting Liu; Juan Jia; Erxiong Zhu; Chengzhu Liu; Yunpeng Zhao; Ya Wang; Enze Kang; Jun Xiao; Wei Li (Science China Earth Sciences, 2024)

Removal of cefuroxime from aqueous solution by biochars derived from antibiotic mycelial residue - Xiaoli Ren; Yingfu Li; Tao Feng; Juan Lei; Lijun Cheng (Environmental Science and Pollution Research, 2024)

Phytochemical and biological studies on rare and endangered plants endemic to China. Part XXXVI. Tsugaforrestiacids A–O: Structurally diverse C-18 carboxylated diterpenoids from the twigs and needles of the ‘vulnerable’ conifer and their inhibitory effects on ATP-citrate lyase - Peng-Jun Zhou; Ze-Yu Zhao; Jin-Xin Zhu; Yi Zang; Menny M. Benjamin; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry, 2024)

Environmental water-mediated dual-mechanism regulation of PtCuδ-MnOx-catalyzed acetone oxidation: Enhancement of MvK and inhibition of L-H mechanism - Lei Wang; Xin Zhang; Yonggang Sun; Yulong Ma; Min Xu; Juan Zhang; Yingbo Zhu; Li Zhu; Song Qiao; Jing Ma; Jinpeng Wei; Feng Lin (Journal of Environmental Chemical Engineering, 2024)

Alkali pretreatment-assisted catalytic pyrolysis of waste cellulose acetate for selective preparation of levoglucosenone - Shi-Yu Feng; Sheng Li; Wan-Zhao Huang; Qi Niu; Deng-Yu Chen; Zhi-Mo Fang; Li-Juan Gao; Kai Li; Qiang Lu (Journal of Environmental Chemical Engineering, 2024)

DAS seismic signal recovery with non-uniform noise based on high-low level feature fusion model - Juan Li; Yilong Chen; Yue Li; Qiankun Feng (Journal of Applied Geophysics, 2024)

Genome sequencing analysis and validation of infestation-related functional genes of Vibrio parahaemolyticus LG2206 isolated from the hepatopancreas of diseased mud crab (Scylla paramamosain) in South China - Liu Guangxin; Liu Guangfeng; Li Ce; Ma Hongling; Deng Yiqin; Cheng Changhong; Jiang Jianjun; Fan Sigang; Feng Juan; Lin Li; Qin Zhendong; Guo Zhixun (Fish & Shellfish Immunology, 2024)

Viral capsid-mediated efficient cell labeling of micron-sized magnetic particles for highly sensitive long-term in vivo tumor cells MRI tracking - Xiayi Feng; Ding Gao; Juan Zhou; Zhu Gui; Aoling Cai; Jie Wang; Ji Dai; Yipeng Jing; Junchao Qian; Zongqiang Cui; Lanxiang Li; Yue You; et al. (Chemical Engineering Journal, 2024)

Impact of a Three-Dimensional Reference State in a Global Semi-Implicit Semi-Lagrangian Non-Hydrostatic Atmospheric Model on Yin–Yang Grids - Yifan Zhao; Xindong Peng; Dehui Chen; Yerong Feng; Xiaohan Li; Juan Gu (Journal of Meteorological Research, 2024)

Selective catalytic reduction of NOx with methane over cobalt-exchanged SSZ-39 zeolite - Jian Li; Lunjia Zhang; Ye Ma; Kai Fan; Juan Zhang; Jianping Wu; Wenfu Yan; Xiangju Meng; Qinming Wu; Fan Yang; Feng-Shou Xiao (Chemical Engineering Journal, 2024)

Dietary chitosan reversed the toxic effects of polystyrene microplastics on Nile tilapia (Oreochromis niloticus) liver by inhibiting mitochondrial damage - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Hua Wen; Shan Zhong; Yun-feng Li; Ming Jiang (Reviews in Fish Biology and Fisheries, 2024)

Ultrafast DNA detection based on turn-back loop primer-accelerated LAMP (TLAMP) - Jinyi Shi; Sheng Ding; Chen Li; Gangyi Chen; Feng Du; Sifan Wang; Aiqin Yue; Kaiyuan Ren; Zhirong Yang; Pei Xu; Juan Dong; Jinzhong Zhao; et al. (Analytica Chimica Acta, 2024)

Corrigendum to “Global evapotranspiration from high-elevation mountains has decreased significantly at a rate of 3.923 %/a over the last 22 years” [Sci. Total Environ. 931 (2024) 172804] - Yunying Wang; Zongxing Li; Qi Feng; Lanping Si; Juan Gui; Qiao Cui; Yue Zhao; Chong Xu (Science of The Total Environment, 2024)

High-pressure mafic granulite and supracrustal rocks in the southern Hengshan area, North China Craton: Metamorphic P-T-t evolution and geotectonic significance - Guo-Dong Wang; Xiao-Lei Wang; Zhen M.G. Li; Yue Guan; Juan Wang; Feng-Li Shao; Chun-Ming Wu (Precambrian Research, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Inhibition of ER stress using tauroursodeoxycholic acid rescues obesity-evoked cardiac remodeling and contractile anomalies through regulation of ferroptosis - Feng-Juan Li; Miyesaier Abudureyimu; Zeng-Hui Zhang; Jun Tao; Asli F. Ceylan; Jie Lin; Wei Yu; Russel J. Reiter; Milad Ashrafizadeh; Jun Guo; Jun Ren (Chemico-Biological Interactions, 2024)

Genomic analysis of Clostridium perfringens type D isolates from goat farms - Hang Feng; Ke Wu; Yuan Yuan; Mingjin Fang; Juan Wang; Ruichao Li; Rong Zhang; Xinglong Wang; Dongyang Ye; Zengqi Yang (Veterinary Microbiology, 2024)

An experimental investigation on the foam proportion for coal dust suppression in underground coal mines - Hongsheng Li; Panpan Xu; Songyong Liu; Juan Wang; Lei Zhang; Huifu Ji; Feng Guo; Ge Li (Process Safety and Environmental Protection, 2024)

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Tracing the centennial variation of East Asian Summer Monsoon - Heng Fu; Feng Shi; Wei Liu; Huihong Xue; Wenmin Man; Juan Li; Zhengtang Guo (Global and Planetary Change, 2024)

Indole-3-acetic acid regulating the initial adhesion of microalgae in biofilm formation - Zhihuai Xie; Zixuan Ou; Meili Zhang; Guotao Tang; Xiaoshi Cheng; Wangbei Cao; Jingyang Luo; Fang Fang; Yingqiang Sun; Ming Li; Juan Cai; Qian Feng (Environmental Research, 2024)

RETRACTED: Global evapotranspiration from high-elevation mountains has decreased significantly at a rate of 3.923 %/a over the last 22 years - Yunying Wang; Zongxing Li; Qi Feng; Lanping Si; Juan Gui; Qiao Cui; Yue Zhao; Chong Xu (Science of The Total Environment, 2024)

Annamiacids A and B: Two dissymmetric bis-diterpenes containing a rare ketal-γ-lactone motif from Podocarpus annamiensis and their inhibitory effects on ATP-citrate lyase - Chi Song; Ze-Yu Zhao; Jin-Xin Zhu; Yi Zang; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry Letters, 2024)

Anemhupehins D F, sterols and chromone derivative from Anemone hupehensis and their anti-inflammatory activity - Jin-Lei Ning; Ning Qin; Hong-Fei Li; Xi-Yue Ma; Fei Zhang; Tao Feng; Juan He (Phytochemistry Letters, 2024)

A muti-modal feature fusion method based on deep learning for predicting immunotherapy response - Xiong Li; Xuan Feng; Juan Zhou; Yuchao Luo; Xiao Chen; Jiapeng Zhao; Haowen Chen; Guoming Xiong; Guoliang Luo (Journal of Theoretical Biology, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Effects of Rhizosphere Microorganisms Associated with Suaeda Salsa on the Growth and Salt Stress Resistance of Alfalfa - Jinxia Chen; Qian Zhang; Xihu Qie; Yajuan Che; Dantong Lv; Yuxuan Gao; Fuhong Miao; Shuo Li; Feng He; Juan Sun; Chao Yang (Journal of Soil Science and Plant Nutrition, 2024)

Do CMIP6 models capture the observed anomalous asymmetric Hadley circulation during historical El Niño decaying stage - Xuanliang Ji; Juan Feng; Jianping Li; Chunzai Wang (Climate Dynamics, 2024)

Evaluation and attribution of shortwave feedbacks to ENSO in CMIP6 models - Junjie Huang; Lijuan Li; Yujun He; Haiyan Ran; Juan Liu; Bin Wang; Tao Feng; Youli Chang; Yimin Liu (Climate Dynamics, 2024)

Performance on adsorption of toluene by ionic liquid-modified AC in high-humidity exhaust gas - Ji-feng Guo; Zhao-li Ping; Nan Liu; Xin Zhang; Jia-lin Lv; Yan-yan Yao; Jia-jun Hu; Wen-juan Wang; Ji-xiang Li (Environmental Science and Pollution Research, 2024)

Morphological characteristics, genetic diversity, and ethnobotanical uses of Citrus hongheensis (Rutaceae), an endangered species - Feng-Juan Mou; Jian-Qin Li; Yu-Hong Gao; Yue-Yan Li; Ting-Yao Meng; Shun-Long Han (Plant Biosystems, 2024)

Comparative profiling of the skin and gut microbiota during metamorphosis in Chinese spiny frogs (Quasipaa spinosa) highlights microbial communities involved in disease pathogenesis - Yang Xu; Yun Jiang; Jin-Liang Hou; Juan Li; Xing-Lang Feng; Xin-Hua Liu; De-Liang Li; Jian-Guo Xiang; Jun-Hua Li (Aquaculture, 2024)

Characteristics of Trypsin genes and their roles in insecticide resistance based on omics and functional analyses in the malaria vector Anopheles sinensis - Xiang-Ying Li; Feng-Ling Si; Xiao-Xiao Zhang; Yu-Juan Zhang; Bin Chen (Pesticide Biochemistry and Physiology, 2024)

Role of bipyridyl in enhancing ferrate oxidation toward micropollutants - Juan Li; Jiachun Cao; Maoju Jiang; Linqian An; Ge Zeng; Jiamin Mai; Peng Su; Binghua Jing; Mingbao Feng; Zhimin Ao; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Influences of hydrophobic tail length tuning of linear aliphatic di-cation functioned anion exchange membrane on electrodialysis desalination - Zihao Feng; Jinshuai Liu; Manru Liu; Juan Wang; Xiuhua Li; Yigang Yu (Desalination, 2024)

Effects of di-ions structure of the core layer ionomer on anion exchange membrane characteristics of anti-protein fouling and electrodialysis desalination - Juan Wang; Manru Liu; Zihao Feng; Jinshuai Liu; Xiuhua Li; Yigang Yu (Desalination, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

The impact of volatiles on tick-host interaction and vector competence - Ming-Zhu Zhang; Juan Wang; Li-Feng Du; Pei-Jun He; Na Jia (Current Opinion in Insect Science, 2024)

Modulation of the link between the Hadley circulation and the meridional structure of tropical SSTs by the Atlantic multidecadal oscillation - Ran An; Jianping Li; Juan Feng (Atmospheric Research, 2024)

Progress of 3-ketosteroid Δ1-dehydrogenases for steroid production - Bo Zhang; Deng-Feng Zhou; Meng-Juan Li; Jia-Hui Lan; Hui Li; Ming-Long Shao; Zhi-Qiang Liu; Yu-Guo Zheng (Systems Microbiology and Biomanufacturing, 2024)

Aralianudaside A, an unusual skeleton triterpenoid saponin with anti-airway inflammatory activity from Aralia elata - Pengcheng Yin; Haishan Qian; Shaohua Li; Benqin Tang; Juan Wang; Shuai Chen; Guanghui Ni; Fawu Dong; Yanping Li; Feng Huang; Rongping Zhang; Hongping He; et al. (Natural Product Research, 2024)

Terricoxanthones A–E, unprecedented dihydropyran-containing dimeric xanthones from the endophytic fungus Neurospora terricola HDF-Br-2 associated with the vulnerable conifer Pseudotsuga gaussenii - Hao-Wei Chen; Xi-Ying Wu; Ze-Yu Zhao; Zi-Qi Huang; Xin-Sheng Lei; Guo-Xun Yang; Jiyang Li; Juan Xiong; Jin-Feng Hu (Phytochemistry, 2024)

T-2 toxin induces mitochondrial dysfunction in chondrocytes via the p53-cyclophilin D pathway - Fang-fang Yu; Shui-yuan Yu; Lei Sun; Juan Zuo; Kang-ting Luo; Miao Wang; Xiao-li Fu; Feng Zhang; Hui Huang; Guo-yu Zhou; Yan-jie Wang; Yue Ba (Journal of Hazardous Materials, 2024)

The effect of the mitochondria-targeted antioxidant Mito-tempo during sperm ultra-rapid freezing - Chun-Yuan Li; Juan Liu; Qi-Yuan Zheng; Nian Liu; Xi-Ling Huang; Yu-Yin Wu; Xing-Feng Yao; Qing-Ying Tan; Ying Huang; Chuan-Huo Hu; Chang-Long Xu (Cryobiology, 2024)

Genetic Composition of the High-Quality Winter Wheat Varieties ‘Xinmai 26’ and ‘Xinmai 45’ - Li-Juan Yang; Jian Ma; Da-Le Zhang; Hai-Feng Yang; Yan-Qi Dong; Zeng-Jun Qi; Meng-Jiao Li; Zhi-Kai Jiang; Hua-Ping Ma (Plant Molecular Biology Reporter, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Neoproterozoic Buchan-type metamorphism of the northwestern margin of the Yangtze Craton and tectonothermal implications - Guo-Dong Wang; Zhen M.G. Li; Qian W.L. Zhang; Juan Wang; Feng-Li Shao (Precambrian Research, 2024)

Liriogerphines E–U, further unique sesquiterpene-alkaloid hybrids from the rare Chinese tulip tree - Yu-Hang He; Hong Xiang; Qi-Xiu Li; Yu-Fei Wu; Ze-Xin Jin; Jin-Feng Hu; Yi-Cheng Mao; Juan Xiong (Phytochemistry, 2024)

Occurrence of iodinated contrast media (ICM) in water environments and their control strategies with a particular focus on iodinated by-products formation: A comprehensive review - Hao Yan; Tao Zhang; Yi Yang; Juan Li; Yongze Liu; Dan Qu; Li Feng; Liqiu Zhang (Journal of Environmental Management, 2024)

Durability assessment of hybrid double-skin tubular columns (DSTCs) under simulated marine environments - Jun-Jie Zeng; Zhi-Hao Hao; Xiong-Chao Liang; Jia-Luo Li; Yan Zhuge; Feng Liu; Li-Juan Li (Engineering Structures, 2024)

Revitalizing mitochondrial function and empowering spinal cord recovery using copper-catalyzed Pdots - Bao-Feng Zhao; Fan Wang; Jia-Chen Sun; Jin-Peng Gao; Li-Juan Zhao; Zhao-Liang Shen; Zhi-Peng Li; Yi-Xuan Wang; Yuan Wang; Dan Li; Xi-Fan Mei (Chemical Engineering Journal, 2024)

Global retrieval of the spectrum of terrestrial chlorophyll fluorescence: First results with TROPOMI - Feng Zhao; Weiwei Ma; Jun Zhao; Yiqing Guo; Mateen Tariq; Juan Li (Remote Sensing of Environment, 2024)

Review: Research progress on seasonal succession of phyllosphere microorganisms - Wen-Feng Huang; Juan Li; Jian-An Huang; Zhong-Hua Liu; Li-Gui Xiong (Plant Science, 2024)

Isolation and characterization of Bacillus cereus bacteriophage DZ1 and its application in foods - Zhichao Huang; Xiaoming Yuan; Zhenjun Zhu; Ying Feng; Na Li; Shubo Yu; Chun Li; Bo Chen; Shi Wu; Qihui Gu; Jumei Zhang; Juan Wang; et al. (Food Chemistry, 2024)

Gaseous signaling molecule H2S as a multitasking signal molecule in ROS metabolism of Oryza sativa under thiocyanate (SCN−) pollution - Yu-Xi Feng; Peng Tian; Yu-Juan Lin; Dan-Yang Cao; Cheng-Zhi Li; Abid Ullah (Environmental Pollution, 2024)

Long-Life flexible mild Ag-Zn fibrous battery with bifunctional gel electrolyte - Yanzhe Zhu; Jiajun Fan; Shuo Zhang; Ziheng Feng; Chao Liu; Renbo Zhu; Yunjian Liu; Peiyuan Guan; Mengyao Li; Zhaojun Han; Tao Wan; Jianbo Tang; et al. (Chemical Engineering Journal, 2024)

Uncertainties of ENSO-related Regional Hadley Circulation Anomalies within Eight Reanalysis Datasets - Yadi Li; Xichen Li; Juan Feng; Yi Zhou; Wenzhu Wang; Yurong Hou (Advances in Atmospheric Sciences, 2024)

Moderate selenium alleviates the pulmonary function impairment induced by cadmium and lead in adults: A population-based study - Heze Fan; Ying Xiong; Yuzhi Huang; Lijun Wang; Chenbo Xu; Wenyuan Li; Xueying Feng; Yuxuan Yang; Rui Hua; Zihao Wang; Zuyi Yuan; Juan Zhou (Science of The Total Environment, 2023)

Physiological response, microbial diversity characterization, and endophytic bacteria isolation of duckweed under cadmium stress - Xiao Yang; Ai-Juan Tan; Meng-Meng Zheng; Dan Feng; Kang Mao; Gui-Li Yang (Science of The Total Environment, 2023)

Diarylpentanoids and phenylpropanoids from the roots of Anthriscus sylvestris (L.) Hoffm - Yan-ling Liu; Yan-gang Cao; Ying Niu; Ya-juan Zheng; Xu Chen; Ying-jie Ren; Xi-ling Fan; Xiang-da Li; Xin-yi Ma; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2023)

The Anterior Insula and its Projection to the Prelimbic Cortex are Involved in the Regulation of 5-HT-Induced Itch - Juan Yao; Xuan Li; Guang-Yan Wu; Bing Wu; Jun-Hui Long; Pu-Jun Wang; Shu-Lei Liu; Jie Gao; Jian-Feng Sui (Neuroscience Bulletin, 2023)
Itch is an unpleasant sensation that urges people and animals to scratch. Neuroimaging studies on itch have yielded extensive correlations with diverse cortical and subcortical regions, including the insular lobe. However, the role and functional specificity of the insular cortex (IC) and its subdivisions in itch mediation remains unclear. Here, we demonstrated by immunohistochemistry and fiber photometry tests, that neurons in both the anterior insular cortex (AIC) and the posterior insular cortex (PIC) are activated during acute itch processes. Pharmacogenetic experiments revealed that nonselective inhibition of global AIC neurons, or selective inhibition of the activity of glutaminergic neurons in the AIC, reduced the scratching behaviors induced by intradermal injection of 5-hydroxytryptamine (5-HT), but not those induced by compound 48/80. However, both nonselective inhibition of global PIC neurons and selective inhibition of glutaminergic neurons in the PIC failed to affect the itching-scratching behaviors induced by either 5-HT or compound 48/80. In addition, pharmacogenetic inhibition of AIC glutaminergic neurons effectively blocked itch-associated conditioned place aversion behavior, and inhibition of AIC glutaminergic neurons projecting to the prelimbic cortex significantly suppressed 5-HT-evoked scratching. These findings provide preliminary evidence that the AIC is involved, at least partially via aversive emotion mediation, in the regulation of 5-HT-, but not compound 48/80-induced itch.

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

The effect of climate factors on soil total phosphorus in the Three River Headwaters Region is regulated by soil layers - Qiao Cui; Zongxing Li; Qi Feng; Baijuan Zhang; Juan Gui (Journal of Soil Science and Plant Nutrition, 2023)

scFED: Clustering Identifying Cell Types of scRNA-Seq Data Based on Feature Engineering Denoising - Yang Liu; Feng Li; Junliang Shang; Jinxing Liu; Juan Wang; Daohui Ge (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Anti-complement factor H (CFH) autoantibodies could delay pristane-induced lupus nephritis - Lin-Lin Li; Zhong-qiu Luan; Ying Tan; Hui Wang; Xiao-Juan Yu; Zhen Qu; Feng Yu; Min Chen (Immunologic Research, 2023)
Purpose Anti-complement factor H (CFH) autoantibodies could be detected in lupus and its significance remained to be elucidated. Herein, we aimed to explore the roles of anti-CFH autoantibodies based on pristane-induced lupus mice. Methods Twenty-four female Balb/c mice were randomly divided into four groups, with one group injected with pristane (pristane group), one group with pristane and then human CFH (hCFH) (pristane-CFH group) 3 times, and the other two as vertical controls, PBS group and PBS-CFH group. Histopathological analysis was performed six months after pristane administration. Levels of hCFH, anti-CFH autoantibodies and anti-dsDNA antibody were detected. Murine IgG (mIgG) were purified and cross-reactivity, epitopes, subclasses and functional analysis were further evaluated in vitro. Results Immunization with hCFH and subsequent development of anti-CFH autoantibodies significantly attenuated nephritis of pristane-induced lupus, including lower levels of urinary protein and serum creatinine, decreased levels of serum anti-dsDNA antibody, greatly ameliorated renal histopathologic damage, decreased IgG, complements (C1q, C3) deposits and lower inflammatory factor (IL-6) expression in glomerulus. Furthermore, the purified mIgG (contained anti-CFH autoantibodies) could recognize both hCFH and murine CFH, and the epitopes were predominantly located in hCFH short consensus repeats (SCRs) 1–4, 7 and 11–14. The IgG subclasses were predominant IgG1. The autoantibodies could enhance the binding between hCFH and C3b, and increase factor I mediated-C3b lysis in vitro. Conclusion Our results suggested that anti-CFH autoantibodies could attenuate pristane-induced lupus nephritis by increasing bio-functions of CFH on regulating complement activation and controlling inflammation.

Phylogeny and Geographical Derivation of Genus Hildenbrandia Based on Morphological and Molecular Evidence - Fangru Nan; Huiying Zhao; Juan Li; Xudong Liu; Qi Liu; Junping Lv; Jia Feng; Shulian Xie (Journal of Ocean University of China, 2023)

Phosphoproteomic Analysis Reveals the Predominating Cellular Processes and the Involved Key Phosphoproteins Essential for the Proliferation of Toxoplasma gondii - Xin-zhu Chen; Rui-xue Bai; Fei-yu Qin; Hong-juan Peng; Jin-feng Ren; Lang Hu; Yu-di Li; Cheng He (Acta Parasitologica, 2023)

Peptidomic Analysis and Potential Bioactive Peptides Identification Targeting Endometrial Cancer - Hanzi Xu; Shenglong Yuan; Lin Zhou; Huixin Li; Juan Lv; Xiaoyan Shi; Wangfei Wu; Zhijian Feng; Zhen Gong (International Journal of Peptide Research and Therapeutics, 2023)

Enantioselective effect of the chiral fungicide tebuconazole on the microbiota community and antibiotic resistance genes in the soil and earthworm gut - Chao-Feng Li; Yi-Rong Zhang; Zhen-Chao Tan; Hui-Juan Xu; Cheng-Lan Liu (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Quantitative analysis of recharge sources of different runoff types in the source region of Three River - Li Zongjie; Li Zongxing; Feng Qi; Liu Xiaoying; Gui Juan; Xue Jian (Journal of Hydrology, 2023)

Genome-wide identification and expression analysis of the BURP domain-containing genes in Malus domestica - Jiaxuan Ren; Li Feng; Lili Guo; Huimin Gou; Shixiong Lu; Juan Mao (Physiology and Molecular Biology of Plants, 2023)

Comparison and phylogeny on mitochondrial genome of marine and freshwater taxa of genus Hildenbrandia (Florideophyceae, Rhodophyta) - Fangru Nan; Juan Li; Jia Feng; Junping Lü; Qi Liu; Xudong Liu; Shulian Xie (Journal of Oceanology and Limnology, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Co-exposure of polystyrene microplastics influence cadmium trophic transfer along the “lettuce-snail” food chain: Focus on leaf age and the chemical fractionations of Cd in lettuce - Yimin Wang; Xinyue Qian; Juan Chen; Xuyin Yuan; Ningyuan Zhu; Yudong Chen; Tingting Fan; Ming Li; Harry Toland; Zhiwang Feng (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Construction of butyric acid modified porous starch for stabilizing pickering emulsions: Encapsulation of paclitaxel - Yunxiang Ma; Min Li; Zidi Chen; Juan Feng; Ruixi Chen; Zhipeng Wang; Jinfeng Chen; Shenggui Zhang (Food Hydrocolloids, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Monitoring of insecticide resistance for Apolygus lucorum populations in the apple orchard in China - Xueli Wang; Heng Su; Juan Wang; Guoping Li; Hongqiang Feng; Jinyong Zhang (Crop Protection, 2023)

Soil pollution and the invasion of congener Sphagneticola in crop lands - Qaiser Javed; Jianfan Sun; Susan Rutherford; Juan Li; Babar Iqbal; Yan Xiang; Guangqian Ren; Feng He; Linxuan Pan; Yanwen Bo; Wajid Ali Khattak; Daolin Du (Journal of Environmental Management, 2023)

Interactions of arene ruthenium(II) complexes [η6-(C6H6)Ru(pprip)Cl]+ and [η6-(C6H6)Ru(H2iiP)Cl]+ with RNA triplex poly(U)•poly(A)*poly(U) - Feng Yuan; Xiaohua Liu; Juan Li; Lifeng Tan (JBIC Journal of Biological Inorganic Chemistry, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Unprecedented spirodioxynaphthalenes from the endophytic fungus Phyllosticta ligustricola HDF-L-2 derived from the endangered conifer Pseudotsuga gaussenii - Hao-Wei Chen; Chun-Xiao Jiang; Guang-Lei Ma; Xi-Ying Wu; Wei Jiang; Jiyang Li; Yi Zang; Jia Li; Juan Xiong; Jin-Feng Hu (Phytochemistry, 2023)

Squamabietenols A–F, undescribed abietane-O-abietane dimeric diterpenoids from the ornamental conifer Juniperus squamata and their ATP-citrate lyase inhibitory activities - Kai-Yuan Liang; Hao Li; Peng-Jun Zhou; Ze-Yu Zhao; Yi Zang; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry, 2023)

Microplastics exhibit accumulation and horizontal transfer of antibiotic resistance genes - Yue Feng; Jia-Wen Sun; Wei-Wei Shi; Jian-Lu Duan; Xiao-Dong Sun; Li-Juan Feng; Qian Wang; Yu-Dong Gan; Xian-Zheng Yuan (Journal of Environmental Management, 2023)

Ecological conservation pattern based on ecosystem services in the Qilian Mountains, northwest China - Jian Xue; Zongxing Li; Qi Feng; Zongjie Li; Juan Gui; Yuchen Li (Environmental Development, 2023)

Optimization and mechanism of phosphorus removal in plant-biofilm oxidation ditches: Plant uptake, iron plaque adsorption, and rhizosphere regulation - Wen Liu; Feng-Juan Yang; Yong-Ling Zhou; Yi-Yong Li; Hui Liu; Dan A (Ecological Engineering, 2023)

4-OI ameliorates bleomycin-induced pulmonary fibrosis by activating Nrf2 and suppressing macrophage-mediated epithelial-mesenchymal transition - Ya-xian Wu; Ya-ru Zhang; Feng-juan Jiang; Shuai He; Yan-li Zhang; Dan Chen; Ying Tong; Yun-juan Nie; Qing-feng Pang (Inflammation Research, 2023)

Transcriptome analysis reveals the regulatory effects of Bacillus amyloliquefaciens and Bacillus pumilus on immune and digestive related genes in the spleen of weanling black goats - Nanchi Zhang; Juan Li; Li Wang; Yong Wei; Quzhe Emu; Feng Xu; Lin Zhang (Functional & Integrative Genomics, 2023)

Correction to: Interdecadal shift of the El Niño’s modulation on the connection between the Hadley circulation and tropical SST - Mingxin Yu; Juan Feng; Jianping Li; Ran An (Climate Dynamics, 2023)

Sensory evaluation, chemical structures, and threshold concentrations of bitter-tasting compounds in common foodstuffs derived from plants and maillard reaction: A review - He Li; Li-Feng Li; Zhi-Jun Zhang; Chun-Jian Wu; Shu-Juan Yu (Critical Reviews in Food Science and Nutrition, 2023)

Reduced cadmium toxicity in rapeseed via alteration of root properties and accelerated plant growth by a nitrogen-fixing bacterium - Shili Shen; Yinghan Li; Mingbiao Chen; Juan Huang; Feng Liu; Shijie Xie; Liping Kong; Ying Pan (Journal of Hazardous Materials, 2023)

Endoplasmic reticulum stress regulates autophagic response that is involved in Saikosaponin a-induced liver cell damage - Ye-Feng Wang; Rui-Xia Ma; Bin Zou; Jia Li; Yao Yao; Juan Li (Toxicology in Vitro, 2023)

Localized photo-Fenton reaction boosted by spontaneous generation of H2O2 from thin water membrane - Juan Li; Yu Xia; Jingxing Li; Kaixiang Long; Fengjie Chen; Min Feng; ShiShang Guo; Bolei Chen (Journal of Water Process Engineering, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Interdecadal shift of the El Niño’s modulation on the connection between the Hadley circulation and tropical SST - Mingxin Yu; Juan Feng; Jianping Li; Ran An (Climate Dynamics, 2023)

Dietary lysine facilitates muscle growth and mediates flesh quality of Pacific white shrimp (Litopenaeus vannamei) reared in low-salinity water - Meili Wu; Meifeng Li; Hua Wen; Lijuan Yu; Ming Jiang; Xing Lu; Juan Tian; Feng Huang (Aquaculture International, 2023)

Relationships between the Hadley circulation and tropical sea surface temperature with different meridional structures simulated in CMIP6 models - Yan Li; Mengying Du; Juan Feng; Falei Xu; Wenjun Song (Frontiers in Marine Science, 2023)
The variability of the Hadley Circulation (HC) is greatly impacted by the meridional structure of sea surface temperature (SST), which has varied effects depending on its symmetrical or asymmetrical pattern relative to the equator. By using the Coupled Comparison Program International Project Phase 6 (CMIP6) model outputs and reanalysis datasets, this study assesses the capacity of CMIP6 models to simulate the relationship between the HC and tropical SST under different meridional structures, as well as investigates the possible causes for simulation biases. It is shown that the CMIP6 models can successfully reproduce climatological HC, tropical SST, and their spatial patterns of first leading modes under different meridional structures, where the correlation coefficient between simulations and observations reaches 0.8 or above. By comparison, the CMIP6 model outputs exhibit substantial differences in simulating the HC to SST response over the different meridional structures, with obvious inter-model differences. Considering the capability in simulating the HC to tropical SST response, the CMIP6 models are divided into two types, Type I model and Type II model. Models of Type I are those whose simulation results are basically close to the reanalysis data, with the biases being less than 20%. The models of Type II are those whose simulated response ratios are much stronger than those of the reanalysis. It is found that the models of Type II overestimate the intensity of El Niño-Southern Oscillation (ENSO) events, and remarkably underestimate the HC and SST correlation in the equatorial symmetric part, resulting in the inability of the models of Type II to capture the connection of the HC and tropical SST. The results indicate that, the component of the CMIP6 models in reproducing the ENSO events has a considerable impact on the simulation of the HC and tropical SST relationship, which offers recommendations for enhancing the capability of models to simulate large-scale tropical air-sea interactions.

Anti-neuroinflammatory sesquiterpenoids from Chloranthus henryi - Xue-Jiao Wang; Jun-Li Xin; Sheng-Zhou Yu; Li-Long Pan; Jin-Feng Hu; Juan Xiong (Natural Product Research, 2023)

Creation of intermuscular bone-free mutants in amphitriploid gibel carp by editing two duplicated runx2b homeologs - Rui-Hai Gan; Zhi Li; Zhong-Wei Wang; Xi-Yin Li; Yang Wang; Xiao-Juan Zhang; Jin-Feng Tong; Yue Wu; Ling-Yun Xia; Ze-Xia Gao; Li Zhou; Jian-Fang Gui (Aquaculture, 2023)

Single bubble probe atomic force microscope and impinging-jet technique unravel the interfacial interactions controlled by long chain fatty acid in anaerobic digestion - Jian-Lu Duan; Yi Han; Li-Juan Feng; Jing-Ya Ma; Xiao-Dong Sun; Xiao-Yu Liu; Fan-Shu Geng; Jia-Li Jiang; Mei-Yan Liu; Yu-Chen Sun; Pascal Peu; Bing-Jie Ni; et al. (Water Research, 2023)

Transcriptomic and metabolomic profiling reveal the role of BoMYB2 in flavor regulation mechanism and coloration in the postharvest purple cauliflower - Feng Luo; Guo-Bao Niu; Qian Zhou; Li-Jie Wang; Li-Juan Bai; Wen-Zheng Gao (Postharvest Biology and Technology, 2023)

Study on recharge source and influence mechanism of plant water in the Three-River Headwaters Region, China - Zongjie Li; Xiaoying Liu; Zongxing Li; Qi Feng; Mengqing Liu; Bin Xu; Juan Gui; Qiao Cui; Yue Zhao; Jian Xue (Journal of Hydrology, 2023)

Environmentally-friendly biorecovery of manganese from electrolytic manganese residue using a novel Penicillium oxalicum strain Z6-5-1: Kinetics and mechanism - Shuai Zhao; Bo-Wen Zheng; Yu-Cang Wang; Fei He; Li-Juan Wang; Xiong Lin; Xue-Mei Luo; Jia-Xun Feng (Journal of Hazardous Materials, 2023)

An electrostatic force-independent dephosphorylation-driven chemiluminescent biosensor for sensitive and rapid detection of poly(ADP-ribose) polymerase-1 in human breast tissues - Ming-hao Liu; Feng-zheng Li; Wen-jing Liu; Juan Hu; Meng Liu; Chun-Yang Zhang (Chemical Engineering Journal, 2023)

Where does the runoff come from in dry season in the source region of the Yangtze River? - Li Zongjie; Liu Mengqing; Li Zongxing; Feng Qi; Song Ling-Ling; Xu Bin; Liu Xiaoying; Gui Juan (Agricultural and Forest Meteorology, 2023)

Diverse undescribed compounds from the rhizome of Zingiber officinale Rosc. And their anti-inflammatory activity - Xiao-Juan Zhang; Ze-Zhi Li; Zhi-Min Song; Yue-Tong Zhu; Wei-Sheng Feng; Yong-Xian Cheng; Yan-Zhi Wang (Phytochemistry, 2023)

The emergence of novel macrolide resistance island in Macrococcus caseolyticus and Staphylococcus aureus of food origin - Feng Zhang; Shi Wu; Jingsha Dai; Jiahui Huang; Jumei Zhang; Miao Zhao; Dongli Rong; Yuanyu Li; Juan Wang; Moutong Chen; Liang Xue; Yu Ding; et al. (International Journal of Food Microbiology, 2023)

Barium isotope fractionation during slab dehydration: Records from an eclogite-quartz vein system in Dabie orogen - Juan Xu; Wang-Ye Li; Xiao-Feng Gu; Hui-Min Yu; Xiao-Yun Nan; Yi-Xiang Chen; Fang Huang (Geochimica et Cosmochimica Acta, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

Relationship between the hadley circulation and tropical SST meridional structures under different thermal conditions in the indo-pacific warm pool - Xuanliang Ji; Juan Feng; Jianping Li; Xingrong Chen (Frontiers in Marine Science, 2023)
The Hadley circulation (HC), as a thermally driven large-scale meridional circulation, acts a significant role in the changes of global climate. The modulation of Indo-Pacific warm pool (IPWP) thermal conditions on the relationship between the HC and different tropical sea surface temperature (SST) meridional structures was investigated. Based on the two components of HC and SST, one equatorially asymmetric component (HEA for HC, SEA for SST) and one equatorially symmetric component (HES for HC, SES for SST), the connections of HC to different SST variations in the warm and cold IPWP are explored. The result demonstrates that the relationship of the HC to tropical SST is suppressed in the cold IPWP conditions, whereas it is equivalent to the climatology in the warm IPWP conditions. The plausible mechanism is that the cold (warm) IPWP events are in concordance with the La Niña (El Niño) decay phase. The La Niña decay phase are associated with significant equatorially asymmetric SST anomalies within the IPWP, generating an anomalous meridional circulation and favoring a strengthened equatorially asymmetric anomalous meridional circulation. By contrast, the SST anomalies associated with El Niño decay phase are insignificant. The role of La Niña decay conditions in determining the suppressed connection between SST and HC is further verified by exploring the result after 1979. A similar suppressed response contrast has been detected. Therefore, the results demonstrate that warm and cold ENSO events have impacts on the interannual thermal conditions of IPWP, whereby it plays considerable role in impacting the relationship between the HC and tropical SST. Particularly, with the rapid warming, the interconnection between ENSO events and thermal conditions of IPWP under different timescales could be altered, the influence of which on the responses of the HC to tropical SST remains uncertain and is worthy further researching.

Nanoplastics exposure induces vascular malformation by interfering with the VEGFA/VEGFR pathway in zebrafish (Danio rerio) - Lu Dai; Juanjuan Luo; Meilan Feng; Maya Wang; Jiannan Zhang; Xiaoqian Cao; Xiaojun Yang; Juan Li (Chemosphere, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

A review of isotope ecohydrology in the cold regions of Western China - Zhang Baijuan; Li Zongxing; Feng Qi; Zhang Baiting; Gui Juan (Science of The Total Environment, 2023)

Pilot test of low-rank coal pyrolysis coupled with gasification to hydrogen-rich gas for direct reduced iron: Process modeling, simulation and thermodynamic analysis - Qian Liu; Ying-jie Zhao; Yi Huang; Feng Pei; Yang Cui; Li-juan Shi; Li-ping Chang; Qun Yi (Fuel, 2023)

Heterojunction engineering of Ni3S2/NiS nanowire for electrochemical hydrogen evolution - Meng Chen; Qing Su; Nutthaphak Kitiphatpiboon; Juan Zhang; Changrui Feng; Shasha Li; Qiang Zhao; Abuliti Abudula; Yufei Ma; Guoqing Guan (Fuel, 2023)

Highly conductive anion exchange membrane with a stable double-sided anti-fouling structure for electrodialysis desalination of protein systems - Juan Wang; Manru Liu; Zihao Feng; Jinshuai Liu; Shijun Liao; Xiuhua Li; Yigang Yu (Desalination, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

microRNAs shape social immunity: a potential target for biological control of the termite Reticulitermes chinensis - Long Liu; Feng-Ming Yan; Chen-Chen Zhao; Li-Juan Su; Qiu-Ying Huang; Qing-Bo Tang (Journal of Pest Science, 2023)
Eusocial insects can employ various behavioural and physiological disease defences to avoid, resist and tolerate pathogen infections in their closely related and packed colonies, termed social immunity. Recent studies have shown that several molecules serve insect social immunity, including chemical odours, insect venoms, immune-related proteins, etc. However, whether and how microRNAs (miRNAs), whose precursors are processed by Dicer-1 , drive social immunity in insect colonies is still unknown. Here, we used a ‘host–pathogen’ system (host: Reticulitermes chinensis ; pathogen: Metarhizium anisopliae ) to explore the impact of miRNAs on social immunity in termite colonies. We found that RNAi-mediated silencing of Dicer-1 led to decreased miRNA concentration, significantly inhibited carbohydrate and energy metabolism and affected other life processes, such as the immune response and oxidation–reduction reactions, in whole body of the termite. In behavioural defence, silencing Dicer-1 significantly diminished defensive social behaviours such as locomotion, grooming, cannibalism and burial in termite groups when encountering fungal contamination. In physiological defence, Dicer-1 silencing and miR-71-5 stimulation resulted in significantly decreased antifungal activities of termites. Furthermore, both Dicer-1 -silenced and miR-71-5 stimulant-treated termite groups exhibited a high level of mortality during fungal contamination. Our findings demonstrated the important role of miRNAs in shaping social immunity in termite colonies, providing insights necessary to understand the potential mechanisms underlying behavioural and physiological disease defences in insects and hence laying the groundwork for miRNA-based pest control.

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Correction to: Behavioral and brain functional characteristics of children with attention-defcit/hyperactivity disorder and anxiety trait - Zhao-Min Wu; Peng Wang; Juan Liu; Lu Liu; Xiao-Lan Cao; Li Sun; Qing-Jiu Cao; Li Yang; Yu-Feng Wang; Bin-Rang Yang (Brain Imaging and Behavior, 2022)

Behavioral and brain functional characteristics of children with Attention-Deficit/Hyperactivity disorder and anxiety trait - Zhao-Min Wu; Peng Wang; Juan Liu; Lu Liu; Xiao-Lan Cao; Li Sun; Qing-Jiu Cao; Li Yang; Yu-Feng Wang; Bin-Rang Yang (Brain Imaging and Behavior, 2022)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Temporal-spatial variation, source forensics of PAHs and their derivatives in sediment from Songhua River, Northeastern China - Rashid Mohammed; Zi-Feng Zhang; Ying-Hua Hu; Chao Jiang; Zhi-Qiang He; Wen-Juan Wang; Yi-Fan Li (Environmental Geochemistry and Health, 2022)

Modal Identification of Structures by Eliminating the Effect of the High Ocean Wind - Chun-Xu Qu; Chang-Chong Liu; Xiao-Mei Yang; Hui-Juan Liu; Hong-Nan Li; Yu-Feng Zhang (Journal of Marine Science and Engineering, 2022)
Tropical cyclone is a rapidly rotating storm system with severe excitation such as high wind. This severe excitation may change the performance of structures, such as bridges, wharves and wind turbine structures. It is very necessary to monitor this important change. Modal parameters are the ones to reflect the structural instinct behavior. However, many identification methods assume that the excitation is white noise, which is not the truth during high ocean wind excitation. Therefore, the modal identification method to deal with severe ocean wind excitation should be investigated. This paper proposes an innovative method to eliminate the effect of high ocean wind on modal identification. The formulation to generate an impulse response is described, where the effect of high wind is pointed. Then the elimination method is derived using the wind velocity spectrum and correlation function. After the wind field is simulated, the wind velocities and spectra at all accelerometer positions are obtained. The real impulse response form is obtained. Then, modal identification using the real impulse response is performed. Finally, a practical cable-stayed bridge is employed and modal identification is performed. The results show that the identified modes can reflect structural real behavior.

The Location Reliability of the Resting-State fMRI FC of Emotional Regions Towards rTMS Therapy - Na Zhao; Juan Yue; Zi-Jian Feng; Yang Qiao; Qiu Ge; Li-Xia Yuan; Jue Wang; Yu-Tao Xiang; Yu-Feng Zang (Neuroinformatics, 2022)

Identification of a 5-gene-risk score model for predicting luminal A-invasive lobular breast cancer survival - Yi-Huan Chen; Tao-Feng Zhang; Yi-Yuan Liu; Jie-Hua Zheng; Wei-Xun Lin; Yao-Kun Chen; Jie-Hui Cai; Juan Zou; Zhi-Yang Li (Genetica, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

Exogenous Ca2+ Associated with Melatonin Alleviates Drought-Induced Damage in the Woody Tree Dalbergia odorifera - El-Hadji Malick Cisse; Li-Jia Zhang; Yu-Jin Pu; Ling-Feng Miao; Da-Dong Li; Juan Zhang; Fan Yang (Journal of Plant Growth Regulation, 2022)

Occurrence of polycyclic aromatic hydrocarbons (PAHs) in the seafood from an important fishing area in the East China Sea and a comparison between seafood from different origins - Wang Qian; Lu Dequan; Xiong Yiran; Peng Fei; Li Juan-ying; Wu Feng; Chu Yanping; Sun Ruihua; Tian Siquan (Environmental Monitoring and Assessment, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Dietary phosphorus requirement for juvenile bighead carp (Aristichthys nobilis) - Meifeng Li; Li Zhang; Bing Hu; Lei Liu; Feng Huang; Juan Tian; Xianqin Hu; Yuanyuan Wang (Aquaculture International, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Multi-watershed nonpoint source pollution management through coupling Bayesian-based simulation and mechanism-based effluent trading optimization - Xiaomei Xu; Xueting Zeng; Yongping Li; Chunrong Wang; Lei Yu; Guohe Huang; Junlong Zhang; Juan Feng; Xinyu Han (Stochastic Environmental Research and Risk Assessment, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

High-quality Chlorella vulgaris biomass harvesting through chitosan and polyacrylamid2e - Yu Wang; Juan Wang; Chenchen Feng; Jinyang Li; Naike Wang; Jinling Cai (Environmental Science and Pollution Research, 2022)

CitWRKY28 and CitNAC029 promote the synthesis of cuticular wax by activating CitKCS gene expression in citrus fruit - Hongbin Yang; Zhifeng Zhu; Mingfei Zhang; Xin Li; Rangwei Xu; Feng Zhu; Juan Xu; Xiuxin Deng; Yunjiang Cheng (Plant Cell Reports, 2022)

Electrochemical enhancement of high-efficiency wet removal of mercury from flue gas - Nai-jiao Xu; Sen Li; Yu-hong Fu; Zhao-yang Wang; Li-juan Feng; Ji Wang (Environmental Science and Pollution Research, 2022)

Influence of the NAO on Wintertime Surface Air Temperature over East Asia: Multidecadal Variability and Decadal Prediction - Jianping Li; Tiejun Xie; Xinxin Tang; Hao Wang; Cheng Sun; Juan Feng; Fei Zheng; Ruiqiang Ding (Advances in Atmospheric Sciences, 2022)
In this paper, we investigate the influence of the winter NAO on the multidecadal variability of winter East Asian surface air temperature (EASAT) and EASAT decadal prediction. The observational analysis shows that the winter EASAT and East Asian minimum SAT (EAmSAT) display strong in-phase fluctuations and a significant 60–80-year multidecadal variability, apart from a long-term warming trend. The winter EASAT experienced a decreasing trend in the last two decades, which is consistent with the occurrence of extremely cold events in East Asia winters in recent years. The winter NAO leads the detrended winter EASAT by 12–18 years with the greatest significant positive correlation at the lead time of 15 years. Further analysis shows that ENSO may affect winter EASAT interannual variability, but does not affect the robust lead relationship between the winter NAO and EASAT. We present the coupled oceanic-atmospheric bridge (COAB) mechanism of the NAO influences on winter EASAT multidecadal variability through its accumulated delayed effect of ∼15 years on the Atlantic Multidecadal Oscillation (AMO) and Africa–Asia multidecadal teleconnection (AAMT) pattern. An NAO-based linear model for predicting winter decadal EASAT is constructed on the principle of the COAB mechanism, with good hindcast performance. The winter EASAT for 2020–34 is predicted to keep on fluctuating downward until ∼2025, implying a high probability of occurrence of extremely cold events in coming winters in East Asia, followed by a sudden turn towards sharp warming. The predicted 2020/21 winter EASAT is almost the same as the 2019/20 winter.

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

East Asian summer monsoon changes in subtropical China since late Pleistocene: Evidence from the Ailuropoda-Stegodon fauna - Zhi-wen Li; Li Sun; Bao-sheng Li; Feng-nian Wang; Ding-ding Du; You-gui Song; Hui-Juan Zhang; Liu-qin Chen; Dan Xu (Journal of Mountain Science, 2022)

Effects of cascade reservoir systems on the longitudinal distribution of sediment characteristics: a case study of the Heihe River Basin - Yu Wang; Bao-long Li; Juan-juan Liu; Qi Feng; Wei Liu; Xu Wang; Yu-hua He (Environmental Science and Pollution Research, 2022)
Spatial variations in grain size parameters can reflect river sediment transport patterns and depositional dynamics. Therefore, 22 surficial sediment samples taken from the Heihe River and its cascade reservoirs were analyzed to better understand the impact of cascade reservoir construction on sediment transport patterns in inland rivers in China. The results showed that the longitudinal distribution of sediment grain size in the Heihe River was significantly affected by the influence of the cascade reservoirs. The retention rate in the cascade reservoir of the Heihe River reached 79% (193.53 Mt/year), which caused most of the fine sand to accumulate in the reservoir, and the sediment fining degree reached approximately 50%. However, the water discharged from the dam caused serious erosion of the riverbed and coarsening of the sediment, and the coarsening degree was approximately 500%. The backwater zone of the reservoir was influenced by both backwater and released water, and the coarsening degree of sediment was approximately 101%. Sedimentary environmental analysis revealed that the characteristics of the sediment grain size in an upstream tributary of the Heihe River were more influenced by source material than by hydrodynamic conditions, while the grain size characteristics of the mainstream sediments were controlled mainly by hydrodynamic conditions. The characteristics of sediment transport in different reaches of the Heihe River were studied, and the results may provide references for the operation of cascade reservoirs and the sediment control of reservoirs.

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Evolutionary characteristics and phylogeny of cotton chloroplast tRNAs - Ning Wang; Wan-Lin Dong; Xiao-Jing Zhang; Tong Zhou; Xiao-Juan Huang; Bao-Guo Li; Jian-Ni Liu; Xiong-Feng Ma; Zhong-Hu Li (Planta, 2021)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Two new isoquinoline alkaloids from the seeds of Nandina domestica - Juan Qin; Sheng-Yuan Zhang; Yu-Bo Zhang; Li-Feng Chen; Neng-Hua Chen; Zhong-Nan Wu; Ding Luo; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2021)

Recent progress of oridonin and its derivatives for cancer therapy and drug resistance - Yong-Feng Guan; Xiu-Juan Liu; Xiao-Jing Pang; Wen-Bo Liu; Guang -Xi Yu; Yin -Ru Li; Yan-Bing Zhang; Jian Song; Sai-Yang Zhang (Medicinal Chemistry Research, 2021)

A signal quality assessment–based ECG waveform delineation method used for wearable monitoring systems - Jialing Xie; Li Peng; Liang Wei; Yushun Gong; Feng Zuo; Juan Wang; Changlin Yin; Yongqin Li (Medical & Biological Engineering & Computing, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Continuous production of fructooligosaccharides by recycling of the thermal-stable β-fructofuranosidase produced by Aspergillus niger - Juan Wang; Jing Zhang; Lu Wang; Hong Liu; Ning Li; Huanxia Zhou; Zhanguo Ning; Weican Zhang; Lushan Wang; Feng Huang; Yaohua Zhong (Biotechnology Letters, 2021)

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

Low-Dose Triptolide Enhanced Activity of Idarubicin Against Acute Myeloid Leukemia Stem-like Cells Via Inhibiting DNA Damage Repair Response - Pengcheng Shi; Jie Zha; Juan Feng; Zhiwu Jiang; Haijun Zhao; Manman Deng; Naying Liao; Peng Li; Yirong Jiang; Haihan Song; Bing Xu (Stem Cell Reviews and Reports, 2021)

The Fe3O4-modified biochar reduces arsenic availability in soil and arsenic accumulation in indica rice (Oryza sativa L.) - Yao Yao; Hang Zhou; Xiu-Lan Yan; Xiao Yang; Kang-Wen Huang; Juan Liu; Li-Juan Li; Jing-Yi Zhang; Jiao-Feng Gu; Yaoyu Zhou; Bo-Han Liao (Environmental Science and Pollution Research, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Spatial variation in macrobenthic assemblages and their relationship with environmental factors in the upstream and midstream regions of the Heihe River Basin, China - Yu Wang; Juan-Juan Liu; Wei Liu; Qi Feng; Bao-long Li; Han Lu; Shuang Wang (Environmental Monitoring and Assessment, 2021)
The Heihe River is a typical inland river under increasing anthropogenic pressure. To explore the characteristics of the macrobenthic assemblages and their relationships with environmental factors in the upstream and midstream regions of this basin, abiotic conditions and macrobenthic assemblages were investigated in the summers of 2018 and 2019. A total of 50 species were collected, and Arthropoda and mollusks were the dominant groups. A significant increase in standing stock was observed from the upstream to midstream, and predators (PR) were the main functional feeding group. A one-way analysis of variance (ANOVA) revealed that the Shannon-Wiener index and Margalef’s index values significantly differed at the spatial scale ( P < 0.05). A redundancy analysis (RDA) and Pearson correlation analysis showed that the spatial heterogeneity of the macrobenthos was influenced by the biochemical oxygen demand (BOD 5 ), water temperature (WT), total nitrogen (TN), salinity, electrical conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), and potassium permanganate index (COD Mn ) ( P < 0.05). The spatial variation of macrobenthos was mainly governed by natural conditions and human disturbances.

Correction to: Suppression of TLR4/NF-κB Signaling Pathway Improves Cerebral Ischemia–Reperfusion Injury in Rats - Hang Zhao; Zhuo Chen; Li-Juan Xie; Gui-Feng Liu (Molecular Neurobiology, 2021)

Characteristics of the linkage between the boreal winter Hadley cell and various tropical sea surface temperature meridional structures - Juan Feng; Jianping Li; Ran An; Yaqi Wang (International Journal of Climatology, 2021)
This paper investigates the asymmetric response of the boreal winter Hadley cell (HC) to the meridional structures of the tropical sea surface temperature (SST) over the period 1979–2016. The variations in the zonal‐mean SST and HC are decomposed into equatorially symmetric (i.e. SES for SST, HES for HC) and equatorially anti‐symmetric (i.e. SEA for SST, HEA for HC) components. The response of the HEA to a given amplitude variation in SEA is stronger (by around three times) than that of the HES to the same amplitude variation in SES; this response ratio for the boreal winter is smaller than that for the annual mean. The variations in boreal winter HEA and HES are both related to the canonical El Niño, but in different regions; that is, the HEA is connected to the tropical Northwest Pacific SST, whereas the HES is linked to the SST over the tropical Eastern Pacific. During the period 1979–2016, warming of the tropical Northwest Pacific SST weakened the HEA and contributed to the decreased response ratio of the boreal winter HC to tropical SST. This point is further supported by examining the situation over the period 1958–2001, during which an interdecadal variation of tropical Northwest Pacific SST modulated the linkage between the boreal winter HC and SST. This observation shows that the warming of Northwest Pacific SST contributes to the decreased sensitivity of the boreal winter HC to SST, raising the possibility that global warming may affect the relationship between the HC and SST. Key Findings The ratio of the Hadley circulation to different SST meridional structures is reduced during boreal winter. The result raises the possibility that the contribution of global warming in impacting the relationship between the Hadley circulation and SST.

Efficient CRISPR/Cas9-mediated gene editing in Guangdong small-ear spotted pig cells using an optimized electrotransfection method - Yan-yan Wei; Qun-mei Zhan; Xiang-xing Zhu; Ai-fen Yan; Juan Feng; Lian Liu; Jian-hao Li; Dong-sheng Tang (Biotechnology Letters, 2020)

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

Postchemotherapy hippocampal functional connectivity patterns in patients with breast cancer: a longitudinal resting state functional MR imaging study - Yun Feng; Dilihumaer Tuluhong; Zhao Shi; Li Juan Zheng; Tao Chen; Guang Ming Lu; Shaohua Wang; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Indian Ocean tripole mode and its associated atmospheric and oceanic processes - Yazhou Zhang; Jianping Li; Sen Zhao; Fei Zheng; Juan Feng; Yang Li; Yidan Xu (Climate Dynamics, 2020)
Differing from the Indian Ocean dipole (IOD) that has sea surface temperature anomalies (SSTAs) of opposing signs over the tropical southeastern and western Indian Ocean, a tripole pattern, characterized by positive (negative) SSTAs over the tropical central (southeastern and western) Indian Ocean, is observed and named the Indian Ocean tripole (IOT). This study proposes the concept of the IOT and further investigates the associated atmospheric and oceanic processes. Using empirical orthogonal function (EOF) analysis, the IOT (IOD) is represented by the third (second) leading mode of the monthly SSTAs in the tropical Indian Ocean, explaining about 8.2% (10.3%) of the total variance. The IOT peaks in boreal summer, while the IOD has its mature phase in boreal fall. The spatio-temporal differences, together with the significant separation of these two EOF patterns, illustrate that the IOT is independent of the IOD. Heat budget diagnoses indicate that the anomalous temperature over the southeastern and western Indian Ocean is mainly generated by the net heat flux during April–May and by the total ocean advection in June–August. In contrast, the anomalous temperature is mainly driven by the advection of the mean temperature by the anomalous current in April and the residual term in May–June over the central Indian Ocean, which is replaced by advection of the anomalous temperature by the mean zonal current in July.

Design and biosynthesis of functional protein nanostructures - Feng Li; Dianbing Wang; Juan Zhou; Dong Men; Xian-En Zhan (Science China Life Sciences, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Abnormal differentiation of regulatory T cells and Th17 cells induced by perinatal bisphenol A exposure in female offspring mice - You-dan Dong; Liang Gao; Feng-juan Wu; Ren Lin; Yuan Meng; Li-hong Jia; Xiao-fei Wang (Molecular & Cellular Toxicology, 2020)

Variability of boreal spring Hadley circulation over the Asian monsoon domain and its relationship with tropical SST - Yaqi Wang; Juan Feng; Jianping Li; Ran An; Lanning Wang (Climate Dynamics, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Hydrogeochemical and isotopic characteristics of surface water and groundwater in the Qinghai Lake catchment (China) - Sihai Liang; Juan Guo; Pan Wu; Yuqing Feng; Xusheng Wang; Guangjun Wang; Weilin Xu; Yinfei Luo; Li Wan (Arabian Journal of Geosciences, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

An inter-basin teleconnection from the North Atlantic to the subarctic North Pacific at multidecadal time scales - Zhanqiu Gong; Cheng Sun; Jianping Li; Juan Feng; Fei Xie; Ruiqiang Ding; Yun Yang; Jiaqing Xue (Climate Dynamics, 2020)

Cytological, genetic, and proteomic analysis of a sesame (Sesamum indicum L.) mutant Siyl-1 with yellow–green leaf color - Tong-Mei Gao; Shuang-Ling Wei; Jing Chen; Yin Wu; Feng Li; Li-Bin Wei; Chun Li; Yan-Juan Zeng; Yuan Tian; Dong-Yong Wang; Hai-Yang Zhang (Genes & Genomics, 2020)
Background Both photosynthetic pigments and chloroplasts in plant leaf cells play an important role in deciding on the photosynthetic capacity and efficiency in plants. Systematical investigating the regulatory mechanism of chloroplast development and chlorophyll (Chl) content variation is necessary for clarifying the photosynthesis mechanism for crops. Objective This study aims to explore the critical regulatory mechanism of leaf color mutation in a yellow–green leaf sesame mutant Siyl - 1 . Methods We performed the genetic analysis of the yellow-green leaf color mutation using the F 2 population of the mutant Siyl - 1 . We compared the morphological structure of the chloroplasts, chlorophyll content of the three genotypes of the mutant F 2 progeny. We performed the two-dimensional gel electrophoresis (2-DE) and compared the protein expression variation between the mutant progeny and the wild type. Results Genetic analysis indicated that there were 3 phenotypes of the F 2 population of the mutant Siyl - 1 , i.e., YY type with light-yellow leaf color (lethal); Yy type with yellow-green leaf color, and yy type with normal green leaf color. The yellow-green mutation was controlled by an incompletely dominant nuclear gene, Siyl - 1 . Compared with the wild genotype, the chloroplast number and the morphological structure in YY and Yy mutant lines varied evidently. The chlorophyll content also significantly decreased ( P < 0.05 ). The 2-DE comparison showed that there were 98 differentially expressed proteins (DEPs) among YY, Yy, and yy lines. All the 98 DEPs were classified into 5 functional groups. Of which 82.7% DEPs proteins belonged to the photosynthesis and energy metabolism group. Conclusion The results revealed the genetic character of yellow-green leaf color mutant Siyl - 1 . 98 DEPs were found in YY and Yy mutant compared with the wild genotype. The regulation pathway related with the yellow leaf trait mutation in sesame was analyzed for the first time. The findings supplied the basic theoretical and gene basis for leaf color and chloroplast development mechanism in sesame.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Anti-bacterial chromones from cultures of the endophytic fungus Bipolaris eleusines - Juan He; Zheng-Hui Li; Hong-Lian Ai; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Cloning and expression analysis of the StCUL1 gene in potato - Peng-Xiang Pang; Li Shi; Xiao-Juan Wang; Yan-Nan Chang; Yong-Ping Luo; Jin-Lin Feng; Hemu Eri; Gang Gao (Journal of Plant Biochemistry and Biotechnology, 2019)

Multi-scaled response of groundwater nitrate contamination to integrated anthropogenic activities in a rapidly urbanizing agricultural catchment - Xinliang Liu; Yi Wang; Yong Li; Feng Liu; Jianlin Shen; Juan Wang; Runlin Xiao; Jinshui Wu (Environmental Science and Pollution Research, 2019)

The relative roles of the South China Sea summer monsoon and ENSO in the Indian Ocean dipole development - Yazhou Zhang; Jianping Li; Jiaqing Xue; Fei Zheng; Renguang Wu; Kyung-Ja Ha; Juan Feng (Climate Dynamics, 2019)

Climate warming alters subsoil but not topsoil carbon dynamics in alpine grassland - Juan Jia; Zhenjiao Cao; Chengzhu Liu; Zhenhua Zhang; Li Lin; Yiyun Wang; Negar Haghipour; Lukas Wacker; Hongyan Bao; Thorston Dittmar; Myrna J. Simpson; Huan Yang; et al. (Global Change Biology, 2019)
Subsoil contains more than half of soil organic carbon (SOC) globally and is conventionally assumed to be relatively unresponsive to warming compared to the topsoil. Here, we show substantial changes in carbon allocation and dynamics of the subsoil but not topsoil in the Qinghai‐Tibetan alpine grasslands over 5 years of warming. Specifically, warming enhanced the accumulation of newly synthesized ( 14 C‐enriched) carbon in the subsoil slow‐cycling pool (silt‐clay fraction) but promoted the decomposition of plant‐derived lignin in the fast‐cycling pool (macroaggregates). These changes mirrored an accumulation of lipids and sugars at the expense of lignin in the warmed bulk subsoil, likely associated with shortened soil freezing period and a deepening root system. As warming is accompanied by deepening roots in a wide range of ecosystems, root‐driven accrual of slow‐cycling pool may represent an important and overlooked mechanism for a potential long‐term carbon sink at depth. Moreover, given the contrasting sensitivity of SOC dynamics at varied depths, warming studies focusing only on surface soils may vastly misrepresent shifts in ecosystem carbon storage under climate change.

Two highly oxygenated Ergosterols from cultures of the Basidiomycete Conocybe siliginea - Chao-Jun Pu; Yue-Ling Peng; Zheng-Hui Li; Juan He; Rong Huang; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Dissipation of polycyclic aromatic hydrocarbons (PAHs) in soil amended with sewage sludge and sludge compost - Li-Juan Feng; Li-Qiu Zhang; Li Feng; Jia-Li Li (Environmental Science and Pollution Research, 2019)

Glacier change in the Tanggula Mountains, Tibetan Plateau, in 1969–2015 - Hong-yu Duan; Xiao-jun Yao; Shi-yin Liu; Yong-peng Gao; Miao-miao Qi; Juan Liu; Da-hong Zhang; Xiao-feng Li (Journal of Mountain Science, 2019)

Vibralactone Z 4 , the first chain-like vibralactone derivative from cultures of the basidiomycete Boreostereum vibrans - Juan He; Kai-Ting Duan; Zheng-Hui Li; Hong-Lian Ai; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

Performance and Spatial Distribution of Functional Bacteria under Low-Temperature Stress in Biofilm Systems for Polluted Source Water Pretreatment - Guang-feng Yang; Li-juan Feng; Jun Mu; Jing-ya Sun; Liang Zhu; Xiang-yang Xu (International Journal of Environmental Research, 2019)

Effect of El Niño on the response ratio of Hadley circulation to different SST meridional structures - Juan Feng; Jianping Li; Fei-Fei Jin; Zhengyu Liu; Sen Zhao (Climate Dynamics, 2019)

Effect of pyrolysis condition on the adsorption mechanism of heavy metals on tobacco stem biochar in competitive mode - Nan Zhou; Junning Zu; Qiuju Feng; Huanli Chen; Juan Li; Mei-e Zhong; Zhi Zhou; Shuxin Zhuang (Environmental Science and Pollution Research, 2019)

Pathways of Influence of the Northern Hemisphere Mid-high Latitudes on East Asian Climate: A Review - Jianping Li; Fei Zheng; Cheng Sun; Juan Feng; Jing Wang (Advances in Atmospheric Sciences, 2019)

MicroRNA-132-3p represses Smad5 in MC3T3-E1 osteoblastic cells under cyclic tensile stress - MingYan Liu; Fen Sun; YunXia Feng; XinYi Sun; Juan Li; Qiang Fan; Ming Liu (Molecular and Cellular Biochemistry, 2019)

NAO implicated as a predictor of the surface air temperature multidecadal variability over East Asia - Tiejun Xie; Jianping Li; Cheng Sun; Ruiqiang Ding; Kaicun Wang; Chuanfeng Zhao; Juan Feng (Climate Dynamics, 2019)

Overexpression and VIGS system for functional gene validation in oriental melon (Cucumis melo var. makuwa Makino) - Jing Jing Liao; Cheng Hui Wang; Qiao Juan Xing; Yue Peng Li; Xian Feng Liu; Hong Yan Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Influence of the strongest central Pacific El Niño–Southern Oscillation events on the precipitation in eastern China - Yan Li; Baisheng Ma; Juan Feng; Yao Lu (International Journal of Climatology, 2019)
The impact of the strongest central Pacific (CP) El Niño event 2009/2010 and CP La Niña event 1998/1999 from 1979 to 2010 on the precipitation in eastern China has been analysed. During the 2009/2010 CP El Niño event, it is rainy in northern China during maturing winter and decaying spring, but dry during decaying summer. The rainfall centre is located in south China during maturing period and gradually moves northwards, remaining over the Yellow‐Huai River valley during decaying summer. When the 1998/1999 CP La Niña event occurs, northern China is in a state of drought throughout. In south China, dry periods gradually evolve into rainy ones from maturing winter to decaying summer. The two strongest events also have notable impact on the extreme rainfall, and they mainly affect the total rainfall by influencing the extreme precipitation in eastern China. When the 2009/2010 CP El Niño event occurs, the Western Pacific Subtropical High (WPSH) is stronger with a northwards shift, and there is an obvious anticyclonic circulation near the South China Sea and Philippines. Furthermore, during decaying summer, the Pacific–Japan (PJ) wave train shows an eastwards shift comparing to the typical PJ wave train locating from low latitudes to high latitudes, associating with clearly northwardly spreading wave activity fluxes (WAFs) from the equator. When the 1998/1999 CP La Niña event occurs, the WPSH is weaker and retreats eastwards, and there is a noticeable cyclonic circulation around the South China Sea. In decaying spring, the convective activity in the South China Sea is strong, and there are correspondingly significant WAFs spreading from southeastern Asia to north. In decaying summer, northern (southern) China is controlled by anomalous anticyclones (cyclones) with weak (strong) convection, and the WAFs extend northwards to the Yangtze and Huai River valleys.

The contrasting response of Hadley circulation to different meridional structure of sea surface temperature in CMIP5 - Juan Feng; Jianping Li; Jianlei Zhu; Yang Li; Fei Li (Theoretical and Applied Climatology, 2019)

Urbanization effects on changes in the observed air temperatures during 1977–2014 in China - Yuanzheng Li; Lan Wang; Hongxuan Zhou; Guosong Zhao; Feng Ling; Xiaodong Li; Juan Qiu (International Journal of Climatology, 2019)
This study endeavoured to accurately estimate the effects of urbanization on changes in temperatures during 1977–2014 throughout China. To this end, we (a) classified the stations using improved standards, (b) homogenized the mean minimum (Tmin), mean maximum (Tmax), and mean temperature (Tm) data series, (c) identified regions with different temperature trends based on the modified methodology, and analysed the regional changes in the background rural temperatures, (d) explored the relationships between the temperature trend effects of urbanization and the three indices of the urbanization intensity, and (a) calculated the contribution from urbanization on the regional scale. The results indicated the following: (a) After homogenization, several adjustment amplitudes were larger than 1 °C, the maximum value of which reached 7.84 °C. (b) China was divided into six regions with different rural temperature trends. Rural temperatures significantly increased throughout China with annual Tmin, Tmax and Tm changing rates of 0.424, 0.339, and 0.352 °C/decade, respectively. Throughout all of China, the maximum rates for Tmax, Tmin, and Tm occurred during the spring and the minimum rates for Tmax and Tm occurred during the summer, while that for Tmin was slightly lower in the winter than during the summer. (c) Significant correlations did not always exist between the urbanization‐contributed temperature‐changing rates and the indices of urbanization intensity, and the correlation coefficients varied under different conditions. These values were both positive and negative. The changes in the areas of the built‐up regions constituted the best correlation factors. (d) The percentages of the contributions of urbanization to the mean annual Tmin, Tmax, and Tm were −0.08, 0.21, and −0.09%, respectively. These results are beneficial for understanding the effects of urbanization on regional or global climate change to some extent.

An advanced impact of Arctic stratospheric ozone changes on spring precipitation in China - Fei Xie; Xuan Ma; Jianping Li; Jinlong Huang; Wenshou Tian; Jiankai Zhang; Yongyun Hu; Cheng Sun; Xin Zhou; Juan Feng; Yun Yang (Climate Dynamics, 2018)

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor of 30-Day Mortality of Intracerebral Hemorrhage Patients: a Validation Cohort Study - Fei Wang; Li Wang; Ting-ting Jiang; Jian-jun Xia; Feng Xu; Li-juan Shen; Wen-hui Kang; Yong Ding; Li-xia Mei; Xue-feng Ju; Shan-you Hu; Xiao Wu (Neurotoxicity Research, 2018)

Investigation of the rheological behavior of activated sludge in response to CeO2 nanoparticles and potential mechanism - Guoxiang You; Peifang Wang; Jun Hou; Chao Wang; Jin Qian; Yanhui Ao; Juan Chen; Lingzhan Miao; Yi Xu; Tao Feng; Li Tao (Environmental Science and Pollution Research, 2018)

The relationship between putamen-SMA functional connectivity and sensorimotor abnormality in ESRD patients - Dun Ding; Peng Li; Xue-ying Ma; Wang-huan Dun; Shi-feng Yang; Shao-hui Ma; Hong-juan Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Hoeflea prorocentri sp. nov., isolated from a culture of the marine dinoflagellate Prorocentrum mexicanum PM01 - Qiao Yang; Zhi-Wei Jiang; Cheng-Hui Huang; Ruo-Nan Zhang; Ling-Zhi Li; Guang Yang; Li-Juan Feng; Guang-Feng Yang; Heng Zhang; Xiao-Ling Zhang; Jun Mu (Antonie van Leeuwenhoek, 2018)

Effects of Wolbachia infection on the postmating response in Drosophila melanogaster - Zhen He; Hua-Bao Zhang; Shi-Tian Li; Wen-Juan Yu; John Biwot; Xiao-Qiang Yu; Yu Peng; Yu-Feng Wang (Behavioral Ecology and Sociobiology, 2018)

Time is nothing: emotional consistency of autobiographical memory and its neural basis - Rui Xu; Juan Yang; Chunliang Feng; Haiyan Wu; Ruiwang Huang; Qiuli Yang; Zhihao Li; Pengfei Xu; Ruolei Gu; Yue-jia Luo (Brain Imaging and Behavior, 2018)

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

PKM2-dependent metabolic reprogramming in CD4+ T cells is crucial for hyperhomocysteinemia-accelerated atherosclerosis - Silin Lü; Jiacheng Deng; Huiying Liu; Bo Liu; Juan Yang; Yutong Miao; Jing Li; Nan Wang; Changtao Jiang; Qingbo Xu; Xian Wang; Juan Feng (Journal of Molecular Medicine, 2018)

Suppression of TLR4/NF-κB Signaling Pathway Improves Cerebral Ischemia–Reperfusion Injury in Rats - Hang Zhao; Zhuo Chen; Li-Juan Xie; Gui-Feng Liu (Molecular Neurobiology, 2018)

Decadal-scale teleconnection between South Atlantic SST and southeast Australia surface air temperature in austral summer - Jiaqing Xue; Jianping Li; Cheng Sun; Sen Zhao; Jiangyu Mao; Di Dong; Yanjie Li; Juan Feng (Climate Dynamics, 2018)

Safety, pharmacokinetics, and pharmacodynamics of S-(−)-pantoprazole sodium injections after single and multiple intravenous doses in healthy Chinese subjects - Hui-Wen Jiao; Lu-Ning Sun; Yue-Qi Li; Lei Yu; Hong-Wen Zhang; Mei-Feng Wang; Li-Yuan Yu; Zi-Qing-Yun Yuan; Li-Jun Xie; Juan Chen; Ling Meng; Xue-Hui Zhang; et al. (European Journal of Clinical Pharmacology, 2018)

Cross‐Seasonal Influence of the SAM on Southern Hemisphere Extratropical SST and its Relationship with Meridional Circulation in CMIP5 models - Fei Zheng; Jianping Li; Ruiqiang Ding; Juan Feng (International Journal of Climatology, 2018)
Using outputs from the Coupled Model Intercomparison Project Phase 5 (CMIP5) models, the influence of the December–February (DJF) Southern Hemisphere Annular Mode (SAM) on March–May (MAM) zonal‐mean meridional circulation found in reanalysis data is assessed. Considering that the DJF Southern Hemisphere extratropical SST pattern associated with the SAM (SESST hereafter) acts as an important ‘bridge’ in the cross‐seasonal influence of the DJF SAM on MAM meridional circulation, model performance in simulating the influence of the DJF SAM on SESST and in capturing the connection between SESST and MAM meridional circulation are investigated. Most of the models are equipped to capture the influence of the DJF SAM on SESST. However, the model‐simulated influence is stronger than the observations, which is partially attributed to an overestimation of the association between the SAM and surface zonal wind by these models. The simulated cross‐seasonal influence of the DJF SAM on MAM meridional circulation tends to be closer to the observations in models with high performance in depicting the influence of MAM SESST on MAM meridional circulation than in models with relatively low performance.

Underestimated effects of sediments on enhanced startup performance of biofilm systems for polluted source water pretreatment - Zheng-hui Lv; Jing Wang; Guang-feng Yang; Li-juan Feng; Jun Mu; Liang Zhu; Xiang-yang Xu (Biodegradation, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

Release and kinetics of arsenic and plumbum in the Songhua River surficial sediments - Guang-Min Liu; Qing An; Li-Juan Wang; Xin Jia; Si-Hui Feng; Shu-Mei Xia; Yi-Ning Wu; Hong Qi (Environmental Science and Pollution Research, 2018)

RETRACTED ARTICLE: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2017)
Angiogenesis after ischemic brain injury contributes to the restoration of blood supply in the ischemic zone. Strategies to improve angiogenesis may facilitate the function recovery after stroke. Recent researches have demonstrated that dysfunction of long non-coding RNAs are associated with angiogenesis. We have previously reported that long non-coding RNAs (lncRNAs) are aberrantly expressed in ischemic stroke. However, little is known about long non-coding RNAs and theirs role in angiogenesis after stroke. In this study, we identified a rat lncRNAs, Meg3, and found that Meg3 was significantly decreased after ischemic stroke. Overexpression of Meg3 suppressed functional recovery and decreased capillary density after ischemic stroke. Downregulation of Meg3 ameliorated brain lesion and increased angiogenesis after ischemic stroke. Silencing of Meg3 resulted in a proangiogenic effect evidenced by increased endothelial cell migration, proliferation, sprouting, and tube formation. Mechanistically, we showed that Meg3 negatively regulated notch pathway both in vivo and in vitro. Inhibition of notch signaling in endothelial cells reversed the proangiogenic effect induced by Meg3 downregulation. This study revealed the function of Meg3 in ischemic stroke and elucidated its mechanism in angiogenesis after ischemic stroke.

Complete plastid genomes of the genus Ammopiptanthus and identification of a novel 23-kb rearrangement - Lei Feng; Li-Fei Gu; Juan Luo; Ai-Si Fu; Qiong Ding; Siu-Ming Yiu; Jun-Xian He (Conservation Genetics Resources, 2017)

Historical statistics and future changes in long-duration blocking highs in key regions of Eurasia - Yan Li; Peilong Ye; Zhaoxia Pu; Juan Feng; Baisheng Ma; Jinyan Wang (Theoretical and Applied Climatology, 2017)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Decadal Indian Ocean dipolar variability and its relationship with the tropical Pacific - Yun Yang; Jianping Li; Lixin Wu; Yu Kosaka; Yan Du; Cheng Sun; Fei Xie; Juan Feng (Advances in Atmospheric Sciences, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Distribution of heavy metals in maize and mudflat saline soil amended by sewage sludge - Yan-Chao Bai; Wen-Gang Zuo; Hai-Tao Zhao; Li-Juan Mei; Chuan-Hui Gu; Yong-Xiang Guan; Xu-Kui Wang; Min-Jing Gu; Cai-Yun Zang; Yu-Hua Shan; Ke Feng (Journal of Soils and Sediments, 2017)

Characterization of a Triticum aestivum–Dasypyrum villosum T1VS·6BL translocation line and its effect on wheat quality - Mingxing Wen; Yigao Feng; Juan Chen; Tongde Bie; Yuhui Fang; Dongsheng Li; Xiaolin Wen; Aida Chen; Jinhua Cai; Ruiqi Zhang (Brazilian Journal of Botany, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Repellence of the main components from the essential oil of Glycosmis lucida Wall. ex Huang against two stored product insects - Shan-Shan Guo; Wen-Juan Zhang; Kai Yang; Jun-Yu Liang; Chun-Xue You; Cheng-Fang Wang; Yin-Ping Li; Zhu-Feng Geng; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2017)

NMR solution structure study of one saturated sulphur-containing amides from Glycosmis lucida - Zhu-Feng Geng; Kai Yang; Yin-Ping Li; Shan-Shan Guo; Chun-Xue You; Wen-Juan Zhang; Zhe Zhang; Shu-Shan Du (Natural Product Research, 2017)

Citalopram Ameliorates Synaptic Plasticity Deficits in Different Cognition-Associated Brain Regions Induced by Social Isolation in Middle-Aged Rats - Wei-Gang Gong; Yan-Juan Wang; Hong Zhou; Xiao-Li Li; Feng Bai; Qing-Guo Ren; Zhi-Jun Zhang (Molecular Neurobiology, 2017)

Histological evidence that metformin reverses the adverse effects of diabetes on orthodontic tooth movement in rats - Jing Sun; Juan Du; Wei Feng; Boyao Lu; Hongrui Liu; Jie Guo; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2017)

Developmental changes in digestive enzyme activity in American shad, Alosa sapidissima, during early ontogeny - Xiao-Qiang Gao; Zhi-Feng Liu; Chang-Tao Guan; Bin Huang; Ji-Lin Lei; Juan Li; Zheng-Long Guo; Yao-Hui Wang; Lei Hong (Fish Physiology and Biochemistry, 2017)

Temporal and spatial distributions of PBDEs in atmosphere at Shanghai rural regions, China - Yun-Juan Zhu; Dan Sun; Nuo-Er Yang; Yong-Sheng Ding; Wei-Bing Feng; Wen-Jun Hong; Shi-Mao Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2017)

Asymmetry of the winter extra-tropical teleconnections in the Northern Hemisphere associated with two types of ENSO - Juan Feng; Wen Chen; Yanjie Li (Climate Dynamics, 2017)

Prestack density inversion using the Fatti equation constrained by the P- and S-wave impedance and density - Li-Feng Liang; Hong-Bing Zhang; Zhi-Wei Dan; Zi-Qiang Xu; Xiu-Juan Liu; Cheng-Hao Cao (Applied Geophysics, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Effects of saline water irrigation and fertilization regimes on soil microbial metabolic activity - Li -Juan Chen; Qi Feng; Yong-Ping Wei; Chang-Sheng Li; Yan Zhao; Hui-Ya Li; Bao-Gui Zhang (Journal of Soils and Sediments, 2017)

Performance improvement of raw water pretreatment process with pre-inoculation biofilm: feasibility and limiting factors - Guang-feng Yang; Li-juan Feng; Cai-rong Guo; Tian Xia; Xiang-yang Xu; Liang Zhu (Biodegradation, 2017)

Gene expression signatures for phlegm-dampness constitution of Chinese medicine - Lingru Li; Juan Feng; Haiqiang Yao; Lan Xie; Yu Chen; Lingling Yang; Shujuan Hou; Shipeng Zhao; Ranran Sun; Yanling Wu; Tongtong Bai; Yingshuai Li; et al. (Science China Life Sciences, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Frequency of Spontaneous BOLD Signal Differences between Moderate and Late Preterm Newborns and Term Newborns - Xiushuang Wu; Luqing Wei; Nan Wang; Zhangxue Hu; Li Wang; Juan Ma; Shuai Feng; Yue Cai; Xiaopeng Song; Yuan Shi (Neurotoxicity Research, 2016)

Histochemical examination of the effects of high-dose 1,25(OH)2D3 on bone remodeling in young growing rats - Jing Sun; Bao Sun; Wei Wang; Xiuchun Han; Hongrui Liu; Juan Du; Wei Feng; Bo Liu; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2016)

Phosphorylation of Connexin 43 by Cdk5 Modulates Neuronal Migration During Embryonic Brain Development - Guang-Jian Qi; Qiang Chen; Li-Jun Chen; Yang Shu; Lu-Lu Bu; Xiao-Yun Shao; Pei Zhang; Feng-Juan Jiao; Jin Shi; Bo Tian (Molecular Neurobiology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Spatial Variations of Soil Microbial Activities in Saline Groundwater-Irrigated Soil Ecosystem - Li-Juan Chen; Qi Feng; Chang-Sheng Li; You-Xi Song; Wei Liu; Jian-Hua Si; Bao-Gui Zhang (Environmental Management, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

The effect of calcitriol on high mobility group box 1 expression in periodontal ligament cells during orthodontic tooth movement in rats - Jian Cui; Juan Li; Wei Wang; Xiuchun Han; Juan Du; Jing Sun; Wei Feng; Bo Liu; Hongrui Liu; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2016)

Effects of organic matter content and composition on ammonium adsorption in lake sediments - Li Zhang; Shengrui Wang; Lixin Jiao; Yanping Li; Jiachun Yang; Rui Zhang; Shuang Feng; Juan Wang (Environmental Science and Pollution Research, 2016)

The pseudorabies virus DNA polymerase processivity factor UL42 exists as a monomer in vitro and in vivo - Yi-Ping Wang; Li-Ping Huang; Wen-Juan Du; Yan-Wu Wei; De-Li Xia; Hong-Li Wu; Li Feng; Chang-Ming Liu (Archives of Virology, 2016)

Optimizing schemes on dynamic control of reservoir normal elevation in flood season - Xiao-lu Meng; Xiu-juan Liang; Bai-zhong Yan; Wei Li; Long-hao Guo; Bo Feng (Natural Hazards, 2016)

Cotton GhMYB7 is predominantly expressed in developing fibers and regulates secondary cell wall biosynthesis in transgenic Arabidopsis - Junfeng Huang; Feng Chen; Siyu Wu; Juan Li; Wenliang Xu (Science China Life Sciences, 2016)

Investigation of the ASR family in foxtail millet and the role of ASR1 in drought/oxidative stress tolerance - Zhi-Juan Feng; Zhao-Shi Xu; Jiutong Sun; Lian-Cheng Li; Ming Chen; Guang-Xiao Yang; Guang-Yuan He; You-Zhi Ma (Plant Cell Reports, 2016)

Dissimilarity of phytoplankton assemblages in two connected tropical reservoirs: effects of water transportation and environmental filtering - Li-Juan Xiao; Ren Hu; Liang Peng; La-Mei Lei; Yu Feng; Bo-Ping Han (Hydrobiologia, 2016)

Emissions of NO and N2O in wetland microcosms for swine wastewater treatment - Shunan Zhang; Feng Liu; Runlin Xiao; Yong Li; Juan Zhou; Jinshui Wu (Environmental Science and Pollution Research, 2015)

Statistical downscaling model for late-winter rainfall over Southwest China - ChengQing Ruan; JianPing Li; Juan Feng (Science China Earth Sciences, 2015)

Simulation of the equatorially asymmetric mode of the Hadley circulation in CMIP5 models - Juan Feng; Jianping Li; Jianlei Zhu; Fei Li; Cheng Sun (Advances in Atmospheric Sciences, 2015)

Relationships among the monsoon-like southwest Australian circulation, the Southern Annular Mode, and winter rainfall over southwest Western Australia - Juan Feng; Jianping Li; Yun Li; Jianlei Zhu; Fei Xie (Advances in Atmospheric Sciences, 2015)

Bacillus methylotrophicus isolated from the cucumber rhizosphere degrades ferulic acid in soil and affects antioxidant and rhizosphere enzyme activities - Yue Zhang; Xiu-Juan Wang; Shu-Yun Chen; Li-Yuan Guo; Ming-Lei Song; He Feng; Chen Li; Ji-Gang Bai (Plant and Soil, 2015)

Histochemical evidence of zoledronate inhibiting c-src expression and interfering with CD44/OPN-mediated osteoclast adhesion in the tibiae of mice - Hongrui Liu; Jian Cui; Jing Sun; Juan Du; Wei Feng; Bao Sun; Juan Li; Xiuchun Han; Bo Liu; Yimin; Kimimitsu Oda; Norio Amizuka; et al. (Journal of Molecular Histology, 2015)

Altered distribution of HMGB1 in the periodontal ligament of periostin-deficient mice subjected to Waldo’s orthodontic tooth movement - Juan Li; Wei Feng; Bo Liu; Bao Sun; Xiuchun Han; Juan Du; Jing Sun; Yimin; Jian Cui; Jie Guo; Akira Kudo; Norio Amizuka; et al. (Journal of Molecular Histology, 2015)

Unveiling equal importance of two 14‐3‐3 proteins for morphogenesis, conidiation, stress tolerance and virulence of an insect pathogen - Qian Liu; Jin‐Gen Li; Sheng‐Hua Ying; Juan‐Juan Wang; Wen‐Liang Sun; Chao‐Guang Tian; Ming‐Guang Feng (Environmental Microbiology, 2015)
Summary Two conserved 14‐3‐3 proteins orthologous to S accharomyces cerevisiae Bmh 1/2 are poorly understood in filamentous fungi. Here we show that Bmh 1 and Bmh 2 contribute equally to the fundamental biology and physiology of B eauveria bassiana by targeting many sets of proteins/enzymes. Single Bmh deletion caused similar upregulation of another. Excellent knockdown (∼91%) expressions of Bmh 1 in Δ Bmh 2 and Bmh 2 in Δ Bmh 1 resulted in equally more severe multiphenotypic defects than the single deletions, including G 2 / M transition, blastospore size, carbon/nitrogen utilization, conidiation, germination and conidial tolerances to high osmolarity, oxidation, cell wall stress, high temperature and UV ‐ B irradiation. All the deletion and deletion/knockdown mutants showed similar defects in blastospore yield and density, hyphal septation and cell size, hyphal responses to most chemical stresses and virulence. All the defects were evident with altered transcripts of phenotype‐related genes and well restored by each Bmh complementation. Our Bmh 1 ‐ and Bmh 2 ‐specific transcriptomes generated under osmotic and oxidative stresses revealed up to 6% genes differentially expressed by at least twofold in the fungal genome. Many of those were greatly depressed or co‐depressed in Δ Bmh 1 and Δ Bmh 2 . Our findings provide a thorough insight into the functions and complementary effects of the two 14‐3‐3 proteins in the filamentous entomopathogen.

Effect of Drought Stress on Anatomical Structure and Chloroplast Ultrastructure in Leaves of Sugarcane - Feng-Juan Zhang; Kun-Kun Zhang; Cheng-Zhong Du; Jian Li; Yong-Xiu Xing; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Expression of HMGB1 in the periodontal tissue subjected to orthodontic force application by Waldo’s method in mice - Shengyu Lv; Juan Li; Wei Feng; Hongrui Liu; Juan Du; Jing Sun; Jian Cui; Bao Sun; Xiuchun Han; Kimimitsu Oda; Norio Amizuka; Xin Xu; et al. (Journal of Molecular Histology, 2015)

Ground-dwelling arthropod community response to native grassland conversion in a temperate desert of northwestern China - Qi Feng; Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Li-Juan Chen (Journal of Insect Conservation, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Isolation and characterization of polymorphic microsatellite loci from Silurus Lanzhouensis - Yuan-Hao Yang; Feng Wang; Lv-Zhou Wang; Lei Li; Juan-Ning Yang; Yang Li (Conservation Genetics Resources, 2014)

A more sensitive and rapid multiplex RT-PCR assay combining with magnetic nanobeads for simultaneous detection of viruses in sweet potato - Xing-Guang Deng; Feng Zhu; Ying-Juan Chen; Jian Liu; Tong Zhu; Jing-Yi Li; De-Hui Xi; Hong-Hui Lin (European Journal of Plant Pathology, 2014)

Down-regulation of Gli-1 inhibits hepatocellular carcinoma cell migration and invasion - Jing-Song Chen; Hua-Shu Li; Jiong-Qiang Huang; Long-Juan Zhang; Xi-Lin Chen; Qian Wang; Jian Lei; Ju-Tao Feng; Qin Liu; Xiao-Hui Huang (Molecular and Cellular Biochemistry, 2014)

Protective effect of indomethacin in renal ischemia-reperfusion injury in mice - Sheng-hong Zhu; Li-jia Zhou; Hong Jiang; Rong-jun Chen; Chuan Lin; Shi Feng; Juan Jin; Jiang-hua Chen; Jian-yong Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Synthesis of bufalin derivatives with inhibitory activity against prostate cancer cells - Xiao-Feng Yuan; Hai-Yan Tian; Juan Li; Lu Jin; Shu-Tai Jiang; Ken Wing-Keung Liu; Cheng Luo; David A. Middleton; Mikael Esmann; Wen-Cai Ye; Ren-Wang Jiang (Natural Product Research, 2014)

Awareness is essential for differential delay eyeblink conditioning with soft-tone but not loud-tone conditioned stimuli - He Huang; Bing Wu; Qiong Li; Juan Yao; Xuan Li; Yi Yang; Guang-Yan Wu; Jian-Feng Sui (Neuroscience Bulletin, 2014)

Predicting DNA-binding sites of proteins based on sequential and 3D structural information - Bi-Qing Li; Kai-Yan Feng; Juan Ding; Yu-Dong Cai (Molecular Genetics and Genomics, 2014)

Histochemical examination of cathepsin K, MMP1 and MMP2 in compressed periodontal ligament during orthodontic tooth movement in periostin deficient mice - Shengyu Lv; Hongrui Liu; Jian Cui; Tomoka Hasegawa; Hiromi Hongo; Wei Feng; Juan Li; Bao Sun; Akira Kudo; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2014)

Differences in Gene Expression and Regulation during Ontogenetic Phase Change in Apple Seedlings - Yan Gao; Feng Qiu Yang; Xin Cao; Chun Min Li; Yi Wang; Yong Bo Zhao; Guang Juan Zeng; Dong Mei Chen; Zhen Hai Han; Xin Zhong Zhang (Plant Molecular Biology Reporter, 2014)

Characterization of AvaR1, an autoregulator receptor that negatively controls avermectins production in a high avermectin-producing strain - Jian-Bo Wang; Feng Zhang; Jin-Yue Pu; Juan Zhao; Qun-Fei Zhao; Gong-Li Tang (Biotechnology Letters, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Prefrontal Control of Cerebellum-Dependent Associative Motor Learning - Hao Chen; Li Yang; Yan Xu; Guang-yan Wu; Juan Yao; Jun Zhang; Zhi-ru Zhu; Zhi-an Hu; Jian-feng Sui; Bo Hu (The Cerebellum, 2014)

Converting natural vegetation to farmland alters functional structure of ground-dwelling beetles and spiders in a desert oasis - Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Bo-Wen Jin; Li-Juan Chen (Journal of Insect Conservation, 2014)

A WRKY transcription factor from Malus domestica negatively regulates dehydration stress in transgenic Arabidopsis - Guo-feng Duan; Li-juan Li; Qun-long Liu (Acta Physiologiae Plantarum, 2014)

Cell-penetrating fusion peptides OD1 and OD2 interact with Bcr–Abl and influence the growth and apoptosis of K562 cells - Hai-xia Wang; Heng Xiao; Liang Zhong; Kun Tao; Ya-juan Li; Shi-feng Huang; Jian-ping Wen; Wen-li Feng (Molecular and Cellular Biochemistry, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Saccharopolyspora cavernae sp. nov., a novel actinomycete isolated from the Swallow Cave in Yunnan, south-west China - Juan Cheng; Yong-Guang Zhang; Wei Chen; Li Li; Dao-Feng Zhang; Hong-Fei Wang; Xin-Hua Lu; Yan-Qing Duan; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

MK-2206 induces cell cycle arrest and apoptosis in HepG2 cells and sensitizes TRAIL-mediated cell death - Peng Jiao; Yun-Sheng Zhou; Juan-Xia Yang; Ya-Li Zhao; Qiang-Qiang Liu; Chuang Yuan; Feng-Ze Wang (Molecular and Cellular Biochemistry, 2013)

Eremophilane derivatives from Senecio dianthus - Shuai Huang; Xian-li Zhou; Hong-yan Wang; Cui-juan Wang; Xiao-li Zhou; Feng Xiao; Jie Weng (Journal of Natural Medicines, 2013)

Erratum to: Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Anatomical studies of ovule development in the post-bloom pistils of the ‘Zuili’ plum (Prunus salicina Lindl.) - Hui-juan Jia; Xia Yang; Feng-jie He; Bin Li (Journal of Zhejiang University-SCIENCE B, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Cotton PRP5 gene encoding a proline-rich protein is involved in fiber development - Wen-Liang Xu; De-Jing Zhang; Yan-Feng Wu; Li-Xia Qin; Geng-Qing Huang; Juan Li; Long Li; Xue-Bao Li (Plant Molecular Biology, 2013)

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Expression patterns of an isoflavone reductase-like gene and its possible roles in secondary metabolism in Ginkgo biloba - Cheng Hua; Li Linling; Xu Feng; Wang Yan; Yuan Honghui; Wu Conghua; Wang Shaobing; Liao Zhiqin; Hua Juan; Wang Yuping; Cheng Shuiyuan; Cao Fuliang (Plant Cell Reports, 2013)

Tanshinone IIA and astragaloside IV promote the migration of mesenchymal stem cells by up-regulation of CXCR4 - Juan Xie; Huan Wang; Tiebing Song; Zongren Wang; Feng Li; Jing Ma; Jun Chen; Yayun Nan; Hui Yi; Wen Wang (Protoplasma, 2013)

Expression of c-Src and phospho-Src in epithelial ovarian carcinoma - Yong-Wen Huang; Chen Chen; Man-Man Xu; Jun-Dong Li; Juan Xiao; Xiao-Feng Zhu (Molecular and Cellular Biochemistry, 2013)

The emergence of HIV-1 primary drug resistance genotypes among treatment-naïve men who have sex with men in high-prevalence areas in China - Juan Yang; Hui Xing; Jianli Niu; Lingjie Liao; Yuhua Ruan; Xiang He; Yi Feng; Zhe Li; Yiming Shao (Archives of Virology, 2013)

SOD1 gene transfer into paraventricular nucleus attenuates hypertension and sympathetic activity in spontaneously hypertensive rats - Ning Yuan; Feng Zhang; Ling-Li Zhang; Juan Gao; Ye-Bo Zhou; Ying Han; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2013)

Analysis of the genetic effects of prolactin gene polymorphisms on chicken egg production - Hui-Fang Li; Jing-Ting Shu; Yu-Feng Du; Yan-Ju Shan; Kuan-Wei Chen; Xue-Yu Zhang; Wei Han; Wen-Juan Xu (Molecular Biology Reports, 2013)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Role of ROS/RhoA/PI3K/PKB Signaling in NS1619-Mediated Blood–Tumor Barrier Permeability Increase - Yan-Ting Gu; Yi-Xue Xue; Yan-Feng Wang; Jin-Hui Wang; Qian-Ru ShangGuan; Jia-Xu Zhang; Li-Juan Qin (Journal of Molecular Neuroscience, 2012)

Characteristics of an aerobic denitrifier that utilizes ammonium and nitrate simultaneously under the oligotrophic niche - Liang Zhu; Wei Ding; Li-juan Feng; Xin Dai; Xiang-yang Xu (Environmental Science and Pollution Research, 2012)

Methylation pattern of oncogene HRAS gene promoter region and its clinical relevance to urocystic tumorigenesis - Xiao-Feng Sun; Lan Li; Xiu-Juan Li; Wei Shen (Molecular Biology Reports, 2012)

CDH1 gene polymorphisms, plasma CDH1 levels and risk of gastric cancer in a Chinese population - Zhen Zhan; Juan Wu; Jun-feng Zhang; Ya-ping Yang; Shujuan Tong; Chun-bing Zhang; Jin Li; Xue-wen Yang; Wei Dong (Molecular Biology Reports, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Construction of an infectious clone of human adenovirus type 41 - Duo-Ling Chen; Liu-Xin Dong; Meng Li; Xiao-Juan Guo; Min Wang; Xin-Feng Liu; Zhuo-Zhuang Lu; Tao Hung (Archives of Virology, 2012)

A possible cause of decreasing summer rainfall in northeast Australia - Jianping Li; Juan Feng; Yun Li (International Journal of Climatology, 2012)
The NCEP/NCAR reanalysis and precipitation data from the Australian Bureau of Meteorology are used to analyse variability in rainfall during the austral summer (December–March, DJFM) in northeast Australia (NEA). NEA rainfall shows a marked decrease over the past 50 years, mainly in the austral summer. Our analysis reveals that the summer rainfall decrease in NEA is generally an interdecadal phenomenon. The declining trend has an imprint in the tropical Australian summer monsoon (TASM). Not only does TASM have a phase‐to‐phase influence on NEA summer rainfall at the interannual scale, it is also closely linked with interdecadal variation in NEA summer rainfall. Thus, the decrease in NEA at the interdecadal scale could be attributed to corresponding variation in TASM. Moreover, the coupled linkage between TASM and NEA summer rainfall appears to be largely independent of El Niño–Southern Oscillation. One possible reason for the interdecadal weakening trend in TASM is a sustained interdecadal warming trend in sea surface temperature (SST) over the Wharton Basin (100°–130°E, 20°–5°S). When the Wharton Basin is in a cold state, anomalous westerlies occur in the lower troposphere in the TASM region, and cyclonic circulation anomalies and rising flows occur in the low and middle troposphere over NEA, which are associated with a strong TASM situation, consequently favouring enhanced rainfall over NEA; the opposite occurs in the case of a warm Wharton Basin. SST over the Wharton Basin has shown a continuous warming trend over the past 60 years, contributing to the weakening of TASM and, consequently, a decrease in NEA summer rainfall. Copyright © 2011 Royal Meteorological Society

PDTC attenuate LPS-induced kidney injury in systemic lupus erythematosus-prone MRL/lpr Mice - Jin-Xia Zhai; Zhao-Xiang Zhang; Ya-Juan Feng; Shu-Shu Ding; Xing-Hua Wang; Li-Wei Zou; Dong-Qing Ye (Molecular Biology Reports, 2012)

Biofilm formation and microbial community analysis of the simulated river bioreactor for contaminated source water remediation - Xiang-Yang Xu; Li-Juan Feng; Liang Zhu; Jing Xu; Wei Ding; Han-Ying Qi (Environmental Science and Pollution Research, 2012)

Geodermatophilus nigrescens sp. nov., isolated from a dry-hot valley - Guo-Xing Nie; Hong Ming; Shuai Li; En-Min Zhou; Juan Cheng; Tian-Tian Yu; Jing Zhang; Hui-Gen Feng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

An aporphine alkaloid from Nelumbo nucifera as an acetylcholinesterase inhibitor and the primary investigation for structure–activity correlations - Zhong-duo Yang; Xu Zhang; Juan Du; Zhao-jian Ma; Feng Guo; Shuo Li; Xiao-jun Yao (Natural Product Research, 2012)

Genetic polymorphism analysis of killer cell immunoglobulin-like receptor genes in the Chinese Uygur population - Hong-dan Wang; Bo-feng Zhu; Chun-mei Shen; Guo-lian Yuan; Guang Yang; Juan-ning Guo; Jiang-wei Yan; Hai-xia Qin; Jian-xin Guo; Li-ping Zhang; Xiao-qin Jia; Rudolf Lucas (Molecular Biology Reports, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Quantitative structure-activity relationships of antimicrobial fatty acids and derivatives against Staphylococcus aureus - Hui Zhang; Lu Zhang; Li-juan Peng; Xiao-wu Dong; Di Wu; Vivian Chi-Hua Wu; Feng-qin Feng (Journal of Zhejiang University-SCIENCE B, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Identification of neutral alleles at pollen sterility gene loci of cultivated rice (Oryza sativa L.) from wild rice (O. rufipogon Griff.) - Jin Quan Li; Muhammud Qasim Shahid; Jiu Huan Feng; Xiang Dong Liu; Xing Juan Zhao; Yong Gen Lu (Plant Systematics and Evolution, 2012)

Different sperm sources and parameters can influence intracytoplasmic sperm injection outcomes before embryo implantation - Yue-hong Lu; Hui-juan Gao; Bai-jia Li; Ying-ming Zheng; Ying-hui Ye; Yu-li Qian; Chen-ming Xu; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

Proteomic Analysis of Salt Stress Responses in Rice Shoot - Xiao-Juan Li; Ming-Feng Yang; Yi Zhu; Yu Liang; Shi-Hua Shen (Journal of Plant Biology, 2011)

Simultaneous and rapid detection of enteric pathogens from raw milk by multiplex PCR - Yang He; Juan Dai; Yu-Feng Li (World Journal of Microbiology and Biotechnology, 2011)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

Ds-echinoside A, a new triterpene glycoside derived from sea cucumber, exhibits antimetastatic activity via the inhibition of NF-κB-dependent MMP-9 and VEGF expressions - Qin Zhao; Zhi-dong Liu; Yong Xue; Jing-feng Wang; Hui Li; Qing-juan Tang; Yu-ming Wang; Ping Dong; Chang-hu Xue (Journal of Zhejiang University-SCIENCE B, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Blood cells of a sisorid catfish Glyptosternum maculatum (Siluriformes: Sisoridae), in Tibetan Plateau - Hui Juan Zhang; Cong Xin Xie; Da Peng Li; Hai Ping Liu; Xue Feng Yang (Fish Physiology and Biochemistry, 2011)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

Identification of host-defense genes and development of microsatellite markers from ESTs of hard clam Meretrix meretrix - Hong-jun Li; Wei-dong Liu; Xiang-gang Gao; Dan Zhu; Juan Wang; Yun-feng Li; Chong-bo He (Molecular Biology Reports, 2011)

Isolation and identification of a phosphate-solubilizing bacterium Pantoea stewartii subsp. stewartii g6, and effects of temperature, salinity, and pH on its growth under indoor culture conditions - Xiao-Juan Hu; Zhuo-Jia Li; Yu-Cheng Cao; Jun Zhang; Ying-Xue Gong; Yu-Feng Yang (Aquaculture International, 2010)

Sevoflurane postconditioning reduces myocardial reperfusion injury in rat isolated hearts via activation of PI3K/Akt signaling and modulation of Bcl-2 family proteins - Li-na Yu; Jing Yu; Feng-jiang Zhang; Mei-juan Yang; Ting-ting Ding; Jun-kuan Wang; Wei He; Tao Fang; Gang Chen; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of sevoflurane preconditioning and postconditioning on rat myocardial stunning in ischemic reperfusion injury - An-lu Dai; Li-hua Fan; Feng-jiang Zhang; Mei-juan Yang; Jing Yu; Jun-kuan Wang; Tao Fang; Gang Chen; Li-na Yu; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Magma mixing origin for the post-collisional adakitic monzogranite of the Triassic Yangba pluton, Northwestern margin of the South China block: geochemistry, Sr–Nd isotopic, zircon U–Pb dating and Hf isotopic evidences - Jiang-Feng Qin; Shao-Cong Lai; Chun-Rong Diwu; Yin-Juan Ju; Yong-Fei Li (Contributions to Mineralogy and Petrology, 2010)

Distribution, development and proliferation of interstitial cells of Cajal in murine colon: an immunohistochemical study from neonatal to adult life - Juan Han; Wen-Hao Shen; You-Zhao Jiang; Bin Yu; Yang-Tao He; Nan Li; Feng Mei (Histochemistry and Cell Biology, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Association study of a single nucleotide polymorphism in the exon 2 region of toll-like receptor 9 (TLR9) gene with susceptibility to systemic lupus erythematosus among Chinese - Chang-Juan Xu; Wen-Hui Zhang; Hai-Feng Pan; Xiang-Pei Li; Jian-Hua Xu; Dong-Qing Ye (Molecular Biology Reports, 2009)

Relationships between endothelial nitric oxide synthase gene polymorphisms and osteoporosis in postmenopausal women - Shun-zhi Liu; Hong Yan; Wei-kun Hou; Peng Xu; Juan Tian; Li-fang Tian; Bo-feng Zhu; Jie Ma; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2009)

Establishment and characterization of a fibroblast cell line from the Mongolian horse - Lin-feng Li; Wei-jun Guan; Yue Hua; Xiu-juan Bai; Yue-hui Ma (In Vitro Cellular & Developmental Biology - Animal, 2009)

SSR and SCAR mapping of a multiple-allele male-sterile gene in Chinese cabbage (Brassica rapa L.) - Hui Feng; Peng Wei; Zhong-Yun Piao; Zhi-Yong Liu; Cheng-Yu Li; Yu-Gang Wang; Rui-Qin Ji; Shu-Juan Ji; Ting Zou; Su-Ryun Choi; Yong-Pyo Lim (Theoretical and Applied Genetics, 2009)

Selection of scFvs specific for the HepG2 cell line using ribosome display - Lei Zhou; Wei-Ping Mao; Juan Fen; Hong-Yun Liu; Chuan-Jing Wei; Wen-Xiu Li; Feng-Yun Zhou (Journal of Biosciences, 2009)

An age-dependent proliferation is involved in the postnatal development of interstitial cells of Cajal in the small intestine of mice - Feng Mei; Jiang Zhu; Sheng Guo; De-shan Zhou; Juan Han; Bin Yu; Shi-feng Li; Zhong-yong Jiang; Cheng-jie Xiong (Histochemistry and Cell Biology, 2009)

Effects of Low-Molecular-Weight Organic Acids on Gadolinium Accumulation and Transportation in Tomato Plants - Hui-Juan Zhang; Zheng-Gui Wei; Hai-Yan Zhao; Hong-Xia Yang; Hui-Xin Li; Feng Hu (Biological Trace Element Research, 2009)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Characteristics of carbonyl compounds in ambient air of Shanghai, China - Juan Huang; Yanli Feng; Jian Li; Bin Xiong; Jialiang Feng; Sheng Wen; Guoying Sheng; Jiamo Fu; Minghong Wu (Journal of Atmospheric Chemistry, 2008)

Synthesis and evaluation of the 5-fluorouracil-pectin conjugate targeted at the colon - Qing-Wei Wang; Xue-Ying Liu; Li Liu; Juan Feng; Yu-Hua Li; Zhen-Jun Guo; Qi-Bing Mei (Medicinal Chemistry Research, 2007)

Isolation and characterization of a novel cDNA encoding ERF/AP2-type transcription factor OsAP25 from Oryza Sativa L. - Xiao-Yan Fu; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jin-Ge Liu; Li-Juan Wu; Feng Gao; Hong Zhu; Zhao-Kui Guo; Quan-Hong Yao (Biotechnology Letters, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Improving freezing tolerance of transgenic tobacco expressing sucrose: sucrose 1-fructosyltransferase gene from Lactuca sativa - Hui-Juan Li; Ai-Fang Yang; Xue-Cheng Zhang; Feng Gao; Ju-Ren Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)